Genomic characterization of historical Jinlingnan individuals: insights into genetic continuity and trans-Eurasian signals in eastern China - Shuyi Li; Yuchun Wang; Qu Shen; Jinguo Zan; Mengying Han; Zishuai Huang; Rui Wang; Xinyi Wang; Haifeng He; Le Tao; Hao Ma; Kongyang Zhu; et al. (Human Genetics, 2026)

Mechanism of water and nutrient competition between shelterbelts and farmland under different irrigation patterns in the Hexi Corridor oasis area, China - Yulian Hao; Haiyang Xi; Wenju Cheng; Tengfei Yu; Baofeng Li; Tuo Han; Yuqing Chen; Linbo Qu; Zhehui Wang (Soil and Tillage Research, 2026)

Surface shaving proteomics reveals a parasite-encoded protein embedded in the spore filaments of Ameson portunus - Ming Fu; Huimin Zhu; Liyan Wang; Yongliang Wang; Haoran Sun; Musa Makongoro Sabi; Xiaoxiao Huang; Yuanguang Liu; Bing Han; Hongnan Qu (Journal of Invertebrate Pathology, 2026)

Sodium alginate-based dual-network evaporator for high-yield solar steam generation with synergistic salt rejection - Zhenzhen Guo; Junli Ma; Jiameng Zhang; Xu Han; Ji-Chao Wang; Wanqing Zhang; Xinghang Liu; Li Qu; Xianbao Wang (Desalination, 2026)

Enhanced co-pyrolysis gasification of biomass and charcoal via wet grinding with graphite purification wastewater: Thermal reaction kinetics and catalytic mechanisms - Xiaowei Gan; Chenguang Han; Zhengjie Chen; Yakun Zhang; Junyu Qu; Dong Ouyang; Wenhui Ma (Chemical Engineering Journal, 2026)

The impact of deacetylation on the catalytic performance of biomass-based carbon catalysts in the depolarization reaction of sulfur dioxide - Chen Zhao; KunYuan Liu; Hui Han; HuiLi Huang; YongShui Qu; YuGuang Zhou; QuanYuan Wei (Chemical Engineering Journal, 2026)

Elemental profiles and determinants of hair composition in residents of Nanning, China: insights from multivariate and comparative analyses - Ziyang Ding; Guilin Han; Hongcheng Mei; Rui Qu; Di Wang; Wenqian Sun; Na Mi; Jun Zhu (ENGINEERING Environment, 2026)

Spatiotemporal predictive modeling for coastal phytoplankton based on the Tapnet model: A case study in Zhejiang, China - Yan Wei; Haibin Han; Qinglin Mu; Haodi Zhu; Yueyi Qiao; Shaojian Yang; Chaoyi Yu; Na Wei; Hanyan Luo; Luyuan Zhao; Xuping Zhuo; Yufan Yuan; et al. (Marine Pollution Bulletin, 2026)

Selective recognition of hydroquinone over catechol on a stacked leaf-like ZnCo/N-doped porous carbon@polymelamine electrode - Yafeng Jin; Didi Tong; Li Qu; Jin Zhang; Fangming Han; Desheng Ma; Ruilong Zhang; Xiangquan Qin; Chen Li (Journal of Environmental Chemical Engineering, 2026)

Microbial–enzymatic associations with a U-shaped sweet aroma trajectory and the progressive development of woody, herbal, and aged notes during long-term aging of Shoumei white tea - Xingyu Long; Beibei Wen; Xiaobo Liu; Hongying Huang; Luqin Zhu; Taolin Chen; Yongchao Liang; Yongquan Xu; Xiaohong Wang; Jiaojiao Qu; Shumei Han; Jianjun Liu; et al. (Food Research International, 2026)

Polygonatum kingianum polysaccharides ameliorate cognitive impairments in alcohol-exposed obese mice in a sex-specific manner by regulating the gut microbiome and metabolome - Jiayao Lv; Yizhe Qu; Qixin Yan; Ken Cheng; Qingyang Wu; Jiayi Zhang; Xinting Duan; Shanshan Han; Honglei Tian; Lin Shi (Food Research International, 2026)

β-Cyclodextrin-mediated co-encapsulation of peptide PPHG and gallic acid: Synergistic thrombin-inhibitory activity, enhanced stability, and sustained simulated gastrointestinal release - Zi-Han Qu; Zi-Han Liu; Xue-Fu Li; Hai-Bin Ren; Di-Feng Ren; Jun Lu (Food Bioscience, 2026)

Recent advances on MXene nanomaterials-based biosensing technologies and portable analytical devices for detection of food hazard factors - Haofang Liu; Ling Li; Biru Han; Yina Zhao; Manyan Qiu; Qianyu Zhao; Bo Qu; Xianlong Zhang; Yujun Jiang (Trends in Food Science & Technology, 2026)

Flow-induced vibrations of two elastically coupled cylinders in the tandem arrangement - Yang Qu; Linbo Han; Wenjie Xu; Zhongming Hu; Piguang Wang (Ocean Engineering, 2026)

Mixed-Fungi Applications Enhance Litter Decomposition More Strongly in the Soil Profile than on the Ground in a Desert Steppe Ecosystem, Northwestern China - Hao Qu; Meixin Wang; Jing Wu; Guolin Wang; Ming Zhang; Gang Han; Salman Zare; Eduardo Medina-Roldán (Pedobiologia, 2026)

Stage-resolved zinc isotope dynamics in firefighters’ hair after firefighting - Ziyang Ding; Guilin Han; Qian Zhang; Rui Qu; Jian Hu; Di Wang; Wenqian Sun; Ye Zhao (Journal of Hazardous Materials, 2026)

Carbon sequestration performance and microstructural evolution of alkali-activated coal-based solid waste during mineral carbonation - Lei Qin; Han Wang; Pengfei Liu; Jiawei Li; Chengang Sun; Dantong Li; Chao Qu (International Journal of Greenhouse Gas Control, 2026)

Characteristics and drivers of the flash drought: Based on the daily resolution SPEI from the MERRA-2 between 1980 and 2023 - Qianfeng Wang; Changtong Liu; Ying Zhao; Jucong Huang; Wenhua Chen; Virgílio A. Bento; Han Qiu; Sai Qu; Dandan Yu (Global and Planetary Change, 2026)

Rhizosphere soil microbe-mediated nitrogen cycling exhibits differential responses to nitrogen addition among Leymus chinensis genotypes - Yifan Li; Mian Han; Zehang Qu; Ziqing Gong; Tianjun Gao; Jinlong Wang; Anzhi Ren; Nianxi Zhao (European Journal of Soil Biology, 2026)

Biomimetic amino acid-based microspheres for sustainable manufacturing of antibacterial and rechargeable-deodorizing lyocell fibers - Lian-Yi Qu; Jie Zhao; Zi-Han Yin; Ying-Jun Xu (Chemical Engineering Journal, 2026)

Stress-homogenization tailoring via 2D-seed-mediated template growth for high-efficiency perovskite solar cells - Chenyun Wang; Chuanzhen Shang; Bin Zhou; Duo Qu; Shasha Wang; Wei Jia; Linwei Li; Qiang Guo; Ruilin Han; Wenying Zhao; Fan Xu; Jihuai Wu; et al. (Chemical Engineering Journal, 2026)

Synergistic peroxidase-like catalysis and photothermal effect in a polyoxomolybdate@Fe-polydopamine composite for enhanced antibacterial activity - Jing Dong; Tao Yang; Limin Qiao; Yuchun Han; Zhijuan Zhao; Baolong Qu; Xiaoyu Zhang; Hui Zhang; Siqi Li; Shihan Wang; Ruilian Qi; Huanxiang Yuan; et al. (Chemical Engineering Journal, 2026)

Multi-level responses of wind erosion to climate and vegetation in a desert steppe - Bohan Zhang; Zhiguo Li; Shijie Lv; Junran Li; Guodong Han; Zhongwu Wang; Zhiqiang Qu; Cuiping Gao; Guijie Zhang (CATENA, 2026)

Effect of nitrogen doping with different configurations in biomass-derived carbon materials on the catalysis of sulfur dioxide depolarization reaction - Chen Zhao; KunYuan Liu; Hui Han; HuiLi Huang; YuGuang Zhou; YongShui Qu; QuanYuan Wei (Biomass and Bioenergy, 2026)

Role of pyroptosis in melanoma: Molecular mechanisms and therapeutic potentials - Xiao-Han Zhang; Ke Zhang; Xue-Chun Qu; Jing Zhang; Umm E. Laila; Bo Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2026)

Divergent responses of soil organic carbon fractions, aggregation and microbial communities to straw incorporation strategies along temporal and soil depth gradients in Mollisols - Mengmeng Qu; Bowen Zhang; Xinyi Huang; Huancheng Pang; Han Zhang; Song Guan; Sen Dou (Biology and Fertility of Soils, 2026)

Robust source tracing for solid waste via machine learning-enabled mineralogical fingerprinting - Le Lin; Changhai Ren; Shen Qu; Yang Xiao; Yin Li; Xueming Liu; Han Wang; Zhang Lin (Resources, Conservation and Recycling, 2026)

Flow-induced vibro-acoustic response of a rim-driven thruster under oblique inflow - Yin Han; Xudong Li; Jing Fang; Chi Zhang; Yilin Qu (Ocean Engineering, 2026)

Enhancement of heavy metal electrokinetic removal and remediation in copper-zinc mine tailings by the anaerobic fermentation liquid byproduct addition: The synergistic effect of organic bio-acids - Jianru Liu; Xin Zhao; Junyu Chen; Liting Zhai; Lulu Qian; Enfei Qu; Xiaoyu Han (Journal of Environmental Chemical Engineering, 2026)

Microplastics threaten agroecosystem multifunctionality: A global systematic review with national-scale evidence from China - Zhongke Qu; Zexin Meng; Jie Han; Fulai Yan; Feng Wang; Fangyan Zhang; Yiping Wu; Huayang Zhen; Zhaolin Gu (Journal of Environmental Management, 2026)

Microenvironmental reshaping and photosynthetic recovery: Artificial microbial consortium mediated mechanism for tolerance to combined low-temperature and atrazine stress in soybean seedlings - Siyue Han; Yonghui Huang; Binyu Zhao; Yunhe Cui; Yue Tao; Wentao Dang; Yan Zhang; Jianhua Qu; Ying Zhang (Journal of Environmental Sciences, 2026)

Zoning policy performance in China: Network insights from 77 Yellow River counties in Shandong, China - Mimi Gong; Maofang Ran; Qiang Huang; Yan Cheng; Haonan Xia; Yihan Yao; Qian Wang; Wei Xiang; Meiying Jin; Zile Han; Jun Zhai; Xiaomin Li; et al. (Journal of Environmental Sciences, 2026)

The game changer of biofilm in microplastic pollution and potential environmental risks: Unveiling the pivotal roles on surface modification, metal adsorption, and biological uptake - Yun Xiao; Haixia Pan; Meng Zhang; Xiaoyu Han; Hongqin Guo; Xiaochuan Qu; Yutian Shi; Songying Cao; Ning Zhang; Xin Zhao; Baoqin Liu (Environmental Research, 2026)

Phosphorization-induced heterojunction for highly efficient oxygen evolution reaction in seawater electrolysis - Jiaheng Han; Zhiwei Xue; Ziyang Qu; Nana Ren; Dewei Meng; Weixiao Sun; Miao Sun; Xiuxia Meng; Naitao Yang (Chemical Engineering Journal, 2026)

MXene-enhanced self-healing nanocomposite hydrogels with multiple-dynamic-bond crosslinking for motion sensing and information transmission - Ze-Hua Hou; Huan-Jie Che; Zi-Han Jiang; Xing Wu; Jin-Ping Yuan; Jing Li; Jian-Bo Qu (Chemical Engineering Journal, 2026)

Ubiquitin-mediated downregulation of the proteasome subunit ADRM1 mediates in vitro capacitation of bovine spermatozoa - Lipeng Cao; Chunyu Li; Yue Han; Yanqiu Lv; Jie Wang; Xinglin Qu; Yuyang Zhang; Weiyu Gu; Qinglong Xu; Shunfa Yao; Jinwei Lu; Aihui Lv; et al. (Animal Reproduction Science, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Shipborne UAV deployment and search path optimization for long-range maritime search and rescue - Yixuan Wang; Tianyang Lu; Li Yang; Xingru Qu; Peixiu Han (Ocean Engineering, 2026)

Assessing spatiotemporal accessibility and disparities in maritime search and rescue: A case study in cross-national responsibility waters of the East China Sea - Yixuan Wang; Tianyang Lu; Peixiu Han; Xingru Qu (Journal of Transport Geography, 2026)

Flavor enhancement of Grifola frondosa extracts via enzymatic hydrolysis and subsequent Maillard reaction treatment: Volatile compounds and key odorants identification - Zhifang Han; Ran Yang; Lingbo Qu; ChangCheng Zhao; Mouming Zhao; Shiyuan Chang (Food Research International, 2026)

Quantifying provincial contributions to carbon intensity reduction in China’s construction industry: ML-assisted analysis via an integrated LMDI-ANCOVA framework - Yunxiao Yuan; Marko Lovrić; Han Zhang; Muhammad Umer; Xiaoyu Yang; Yu Xu; Mei Qu (Energy and Buildings, 2026)

Baseline and fractionation of rare earth elements in hair of urban residents in Nanning, South China - Hongcheng Mei; Ziyang Ding; Guilin Han; Rui Qu; Xiaoyu Hu; Di Wang; Zhaowei Jie; Wenqian Sun; Jun Zhu (Environmental Geochemistry and Health, 2026)

Changes in Food Web Structure of Hongze Lake During Different Periods of the Eastern Route of the China’s South-to-North Water Diversion Project - Xinlei Yang; Zhining Shi; Han Liu; Wentong Xia; Xiao Qu; Yushun Chen (Fishes, 2026)
As the largest inter-basin water diversion project in eastern China, the Eastern Route of China’s South-to-North Water Diversion Project (ER-SNWDP) plays a crucial role in alleviating water shortages and ensuring regional ecological security. However, large-scale water diversion that uses natural lakes as impounded lakes across different basins has impacted on the structure and function of the original ecosystems. To explore the changes in the food web and ecosystem structure of the impounded lakes during different operation periods of the ER-SNWDP, we constructed Ecopath models for Hongze Lake in 2010–2011 (pre-operation), 2017–2018 (initial operation), and 2023–2024 (operational period). Our results showed that the trophic energy flow in Hongze Lake was dominated by the detrital food chain, with the highest trophic level ranging from 3.06 to 3.50. Energy flows at trophic levels I and II accounted for a high proportion of the total throughput, and the interactions between trophic levels were relatively simple, indicating that Hongze Lake is approaching a mature ecosystem. Compared with the pre-operation period, the average trophic level, food chain length, and energy conversion efficiency of Hongze Lake declined during the initial operation period, but rebounded during the operational period, though still remaining lower than the pre-operation period. Ecosystem stability followed a similar trajectory: the total primary production/total respiration (TPP/TR) and the system omnivory index (SOI) indicated that ecosystem maturity decreased during the initial operation and increased during the operational period. Fishing activities had negative effects on most functional groups during the pre-operation and initial operation periods, whereas the negative effects from zooplankton and non-native species groups increased during the operational period. Based on changes in the food web structure and ecosystem of Hongze Lake across different water diversion periods, we suggest that the management of Hongze Lake should establish precautionary fishing management measures targeting the effects of filter-feeding functional groups and non-native species, optimize the species and quantities of restocking initiatives, prioritize the protection of critical habitat integrity, and implement long-term ecological monitoring.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Conversion of polyethylene to monoaromatics via a tandem catalytic strategy - Zhiye Ma; Ziyu Cen; Tianrui Bi; Weilong Wen; Cong Luo; Zhijuan Zhao; Baolong Qu; Xiaoyu Zhang; Qinglei Meng; Huizhen Liu; Longfei Lin; Buxing Han (Science Bulletin, 2026)

Analysis of the lignin-degrading mechanism of Acrophialophora curvata and optimization of the conditions for its straw degradation - Yingxia Lu; Hailong Zhang; Hongqin Qu; Jiarui Liu; Lan Peng; Chunbo Dong; Yanwei Zhang; Yanfeng Han (Fungal Biology, 2026)

The mitigating effects of N-acetylcysteine on TiO2 nanoparticles-induced toxicity: Efficacy in cytotoxicity reduction in vitro and complexity in vivo - Shunzi Yu; Chenyi Bao; Nana Liu; Bilai Yan; Zaolong Qu; Shengao Chen; Juan Ni; Xihan Guo; Xian Liu; Han Wang (Environmental Toxicology and Pharmacology, 2026)

Thickness-dependent layered PbBiO2Br with local chlorination induced electronic modulation and atomic-site activation for boosted and selective aerobic photo-oxidation - Tong Li; Wenhao Ma; Han Gao; Xiufeng Lu; Tao Guo; Heyun Fu; Shourong Zheng; Danjun Mao; Xiaolei Qu; Zhaoyi Xu (Chemical Engineering Journal, 2026)

Soil nitrogen addition significantly affects genotypic diversity effects on Leymus chinensis population biomass - Yuyao Lei; Yifan Li; Zehang Qu; Mian Han; Ziqing Gong; Jiayi Li; Jinlong Wang; Lei Chen; Anzhi Ren; Nianxi Zhao (Plant Ecology, 2026)

A Review on Treatment Technologies for High-NaHCO3 Produced Water: Principles, Applications, and Future Perspectives - Shenglong Yuan; Huili He; Chengtun Qu; Lei Han; Jiaxuan Liu; Haijie Hu (Environmental Processes, 2026)

Unraveling spatiotemporal inequalities and nonlinear drivers in the sustainable transition of cultivated land use: Evidence from the Yangtze River Delta region, China - Shilei Wang; Xiaobin Jin; Yanbo Qu; Yeting Fan; Jing Liu; Bo Han; Yinkang Zhou (Applied Geography, 2026)

O, S, C isotopic signatures of high-arsenic groundwater in Ngari, Xizang: Seasonal-scale drivers of arsenic release mechanisms - Lian Song; Shehong Li; Jen-How Huang; Fei He; Qiao Han; Jie Liao; Zhenjie Zhao; Ci Ren Qu Ji; Yong Shui (Acta Geochimica, 2026)

Phenolic constituents from the roots of Strobilanthes sarcorrhiza C. Ling and their bioactivity - Mingjie Xu; Yiwei Wu; Taohong Han; Yajing Chen; Lingxia Qu; Yuyan Xu; Yunhan Zhang; Huizhen Yang; Jiaping Fan; Xueli Huang; Ke Yang; Tunhai Xu; et al. (Natural Product Research, 2026)

Highly efficient lithium separation from sodium-rich mother liquor enabled by novel phenylazophenol derivatives - Han Qu; Guofei Li; Zhiwen Cheng; Wanji Zhou; Chao Zhang (Journal of Water Process Engineering, 2026)

Seismic-attribute optimization for improving reservoir prediction integrating the spectral decomposition and automated machine learning - Keyu Ren; Wei Li; Lun Zhao; Wurong Wang; Jincai Wang; Han Wang; Yi Li; Linbo Qu; Dali Yue (Journal of Applied Geophysics, 2026)

Selenium isotopic constraints on biogeochemical cycling of selenium in the Western Pacific Ocean - Yan Chang; Jing Zhang; Ying Wu; Jian-Guo Qu; Jie Jin; Han Su (Geochimica et Cosmochimica Acta, 2026)

Per- and polyfluoroalkyl substances in the environment and human tissue: A critical review of distribution, exposure pathways, and health risks - Zhenyu Zhang; Yuting Liu; Yi Chen; Han Qu; Jiaxue Ma; Mingyue Pang; Bin Wang; Gang Yu (Environmental Pollution, 2026)

Synergistic effect of β-cyclodextrin-functionalized biochar -based bacterial agent on soil lead/cadmium passivation and plant growth promotion - Jianbang Zhu; Qiwen An; Mengning Wang; Irina B. Ivshina; Xu Sun; Jiaqi Liu; Bohao Jing; Yongtao Zhou; Siyue Han; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2026)

The contributions of two fertilization events to the fertilization recovery efficiency in Arabidopsis - Yuan Wang; Yaxiao Liu; Wenhao Li; Han Lu; Li-Jia Qu; Sheng Zhong (Science China Life Sciences, 2026)

Sex and age disparities in goserelin safety: a global pharmacovigilance study - Zizhen Liu; Han Qu; Zuan Li; Shuowen Wang; Zhenghua Wu; Xin Zhao; Guorong Fan; Yuefen Lou (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Prediction of Sound Speed Profiles Under Disturbance of Strong Internal Solitary Waves Using Bidirectional Long Short-Term Memory Network - Hong Yin; Ke Qu; Han Wang; Guangming Li (Journal of Marine Science and Engineering, 2026)
Time-series machine learning models represented by long short-term memory (LSTM) networks provide an effective way to obtain high-precision sound speed profiles (SSPs) quickly and at low cost, which can meet the practical application requirements of underwater sonar systems. However, in sea areas with frequent strong internal solitary waves, the large-amplitude sound speed anomalies caused by them will seriously interfere with model learning in the form of strong outlier features, resulting in a sharp drop in SSP prediction accuracy and significant degradation of the generalization stability and robustness of the model. To address this problem, this paper proposes a time-series SSP prediction method based on a bidirectional long short-term memory (Bi-LSTM) network. First, Empirical Orthogonal Function (EOF) decomposition is used to realize the low-dimensional feature representation of SSPs, and then the bidirectional time-series feature capture capability of Bi-LSTM is used to predict the SSP sequence with large disturbances caused by strong internal solitary waves. Multiple groups of comparative experiments based on the measured temperature chain data in the continental slope area of the South China Sea show that the Bi-LSTM model has a significant improvement in prediction accuracy and robustness compared with the classical LSTM model. Among them, the Bi-LSTM model with EOF decomposition achieves a correlation coefficient of 0.995 and an average Root Mean Square Error (RMSE) as low as 0.387 m/s. Under the condition of internal solitary wave disturbance, the classical LSTM is difficult to effectively capture the large abrupt change in sound speed, while the proposed Bi-LSTM model can still achieve accurate prediction of the SSP in the disturbance section, and has both the feature recognition and evolution prediction capabilities for the strongly nonlinear internal solitary wave process. This method provides effective technical support for the rapid and large-scale reconstruction of the sound speed field under the disturbance of strong internal solitary waves.

Linking Dissolved Oxygen Fluctuations to Acoustic Activity in the Litopenaeus vannamei Under Operational Pond Conditions - Bangchen Yang; Han Huang; Ke Qu (Journal of Marine Science and Engineering, 2026)
Dissolved oxygen (DO) is a primary environmental regulator of shrimp physiology and behavior in intensive aquaculture systems. Whether shrimp acoustic emissions quantitatively reflect oxygen-driven behavioral modulation under operational pond conditions, however, remains uncertain due to the difficulty of isolating biologically relevant signals from complex soundscapes. In this study, passive acoustic monitoring was conducted in commercial outdoor ponds culturing Litopenaeus vannamei. A periodic-coding non-negative matrix factorization approach was applied to separate putative shrimp-associated acoustic components from broadband background noise and to obtain stable time–frequency representations of acoustic activity. Temporal variations in the extracted acoustic intensity were compared with simultaneously measured DO concentrations. Rather than relying on global correlation, phase-specific analyses revealed that the putative shrimp-associated acoustic component exhibited consistent positive associations with DO dynamics during both rising and declining phases, whereas background noise showed only weak and non-coherent relationships with DO. These results indicate that the observed acoustic–oxygen relationship is non-stationary and context-dependent. Given the observational nature of the study and potential confounding influences (e.g., aeration and other environmental factors), these findings, which are based on observations from a single pond over a limited recording period (62.85 h) under specific operational conditions, should be interpreted with caution and regarded as a proof-of-concept rather than evidence of general applicability. Nevertheless, the results are consistent with the hypothesis that population-level acoustic activity may reflect environmentally modulated behavioral responses. This highlights the potential of soundscape-based approaches as non-invasive tools for supporting aquaculture monitoring, while emphasizing the need for further validation under controlled and multi-site conditions.

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Bi-level multi-objective optimization of configuration and scheduling of offshore wind-solar-storage hybrid power system considering demand response - Meng Shao; Yutong Han; Jinwei Sun; Hao Xu; Xiangqi Kong; Huimin Wang; Bingjie Wang; Zhuxiao Shao; Jian Guan; Zezhi Qu (Ocean Engineering, 2026)

Influence of a composite coal-based carbonaceous reducing agent optimized based on caking index on industrial silicon smelting - Xiaowei Gan; Xiaoyue Wang; Zhengjie Chen; Wenhui Ma; Yakun Zhang; Junyu Qu; Chenguang Han; Zirui Li (Fuel, 2026)

Metabolomics-based reveals the relation between internal metabolism and storage quality of sesame harvested by machine at different speeds - Ling-Yu Qu; Shu-Guang Gao; Di-Chen Gong; Jing-Wen Zhao; Yun-Xuan Hu; Xiao-Tian Zhu; Han-Zhe Zhang; Hua-Min Liu; Hong-Mei Miao (Food Research International, 2026)

Research progress and future prospects of cellulose-based composite gas separation membranes from a green sustainability perspective - Han Pei; Jinghui Zhou; Hongge Jia; Chengbao Geng; Mingyu Zhang; Yanqing Qu; Shuangping Xu; Xiaozhou Zhang; Xing Wang; Jingyu Xu (Carbohydrate Polymers, 2026)

Valorization of oily sludge with coal gasification slag via catalytic pyrolysis - Lei Han; Hai-Jie Hu; Jia-Xuan Liu; Tao Yu; Jin-Ling Li; Lan-Ting Ma; Cheng-Tun Qu; Zhong-Wen Liu (Bioresource Technology, 2026)

An integrated strategy for the efficient extraction and stabilization of phycocyanin from Limnospira platensis - Yuan-Yuan Li; Zhen-Wei Shi; Sheng-nan Yin; Hai-Bin Ren; Zi-Han Qu; Di-Feng Ren (Journal of Applied Phycology, 2026)

Feather-Induced Enrichment of Onygenales Triggers Cross-Kingdom Functional Shifts in Soil Fungal Communities - Chengyun Zhang; Hongqin Qu; Haiyan Wang; Yingxia Lu; Xu Li; Qingsong Ran; Chunbo Dong; Yanwei Zhang; Yanfeng Han (Current Microbiology, 2026)

Dual effects of 6PPD at environmentally relevant concentrations on freshwater algae: Multi-omics reveals a shift in survival strategies from lipid-mediated adaptation to carbon-energy reallocation - Yuting Liu; Qin Fan; Bin Wang; Qiang Gao; Yi Chen; Xu Jing; Han Qu; Delin Qi; Mingyue Pang; Wei Wang (Journal of Hazardous Materials, 2026)

The identification of SiMyD88 confirms the presence of a functional TLR-MyD88-IRAK signaling axis in the sea urchin Strongylocentrotus intermedius - Haikun Zhang; Xuewei Qu; Xuan Ding; Guoshun Ren; Vengatesen Thiyagarajan; Xiaolong Chu; Fengchen Liu; Jie Cui; Yifan Qu; Yaqiong Liu; Yijing Han; Baoyu Huang; et al. (Fish & Shellfish Immunology, 2026)

Fluorinated amino covalent organic frameworks for efficient adsorption of per- and polyfluoroalkyl substances in water - Fanke Tong; Ruitong Zhang; Deyan Li; Han Qu; Xiang Li; Qiang Gao; Delin Qi; Shubo Deng; Wei Wang (Environmental Research, 2026)

Ion coordination competition enhanced adsorption strategy for improved thermopower in I−/I3− gel-based thermo-electrochemical cells - Qingxin Ge; Zhou Zhou; Jing Li; Xiangyang Qu; Qiaoqiao Fang; Zhiliang Han; Rongliang Wu; Huaping Wang; Shiyan Chen (Chemical Engineering Journal, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

Bimetallic synergism-driven Au0.75Pt0.25 nanoparticles-modified SnO2 heterojunction nanostructures for ultrasensitive detection of carbonate-based electrolyte leakage gases towards battery safety applications - PeiJiang Cao; LinLong Qu; YuWei Li; Fang Jia; YuXiang Zeng; DeLiang Zhu; ChunFeng Wang; Shun Han; Ming Fang; XinKe Liu; WenJun Liu; Sachin T. Navale (Chemical Engineering Journal, 2026)

GRO‑α Promotes the Proliferation and Migration of Triple-Negative Breast Cancer Cells through AKT-mTOR Signaling Pathway - Shengyang Sun; Lichun Liang; Bing Han; Ziteng Cai; Weiqun Wang; Yikun Qu (Bulletin of Experimental Biology and Medicine, 2026)

Design and performance verification of crab seedling automatic counting equipment based on improved YOLOv11+DeepSORT - Changfeng Tian; Xuan Che; Lei Ge; Zhi Qu; Mengxia Han (Aquacultural Engineering, 2026)

The novel PFOS substitute OBS induces visual developmental toxicity in zebrafish embryos via ferroptosis - Xing Liu; Xinyi Wu; Mingzhu Xia; Yi Fan; Yichun Zhao; Junjie Han; Ruobing Chen; Yuting Peng; Man Qu (Toxicology Letters, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

TRAF7 protects against acute lung injury by promoting K6-linked ubiquitination of AKT - Jia Wang; Meng-Liu Zeng; Ya-Zhou Sun; Xu-Tao Zhang; Xin-Yan Li; Wei-Yi Qu; Wei Li; Jia-Yi Liu; Xu Cheng; Jun Zhang; Han Tian; Hui Liu; et al. (Science Bulletin, 2026)

A watershed-scale perspective: Elucidating the spatiotemporal dynamics and driving mechanisms of nitrate along the Lancang River - Meng Sun; Yufei Bao; Yuchun Wang; Hao Chen; Jiyuan Yu; Jie Wen; Shanze Li; Xiaodong Qu; Nanping Wu; Hanxiao He; Lingxin Han (Journal of Hazardous Materials, 2026)

Investigation on enhancing the reactivity of carbonaceous reducing agents in industrial silicon smelting by utilizing waste biomass: Pyrolysis, catalytic and environmental analysis - Chenguang Han; Zhengjie Chen; Yakun Zhang; Wenhui Ma; Xiaowei Gan; Junyu Qu; Zirui Li (Journal of Environmental Chemical Engineering, 2026)

Kinetic and thermodynamic analyses of multigranular low-rank coal: Synergistic effect of particle size on reactivity and coke properties - Xiaowei Gan; Zhengjie Chen; Wenhui Ma; Yakun Zhang; Junyu Qu; Chenguang Han; Zirui Li (Fuel, 2026)

Seismic performance of the elevator counterweight system based on a substructural shaking table test method - Qinghua Han; Xiaolong Zhang; Yan Lu; Yuteng Cao; Zhe Qu (Engineering Structures, 2026)

Fabrication of robust TBP-P507 microcapsules through in-situ crosslinking with dual aldehydes and their outstanding Li+/Mg2+separation performance in salt lake brines - Chao Zhang; Guofei Li; Han Qu; Tian Xie; Wanji Zhou; Shiai Xu; Zheng Li (Desalination, 2026)

High-efficiency combustion of boron composites via DAAF-driven B₂O₃ removal and agglomeration suppression - Yang Li; Huan-Yu Hu; Han Li; Ying Qu; Yun-Yang Liu; Qi-Long Yan; Qing-Hua Zhang (Chemical Engineering Journal, 2026)

Quorum sensing enhanced dissimilatory nitrate reduction to ammonia processes in constructed wetland-microbial fuel cells - Shuyuan Zhao; Jun Yan; Mengli Chen; Fucheng Guo; Wen-bo Nie; Jun Li; Han Qu; Yi Chen (Bioresource Technology, 2026)

Two novel TRAF homologs are implicated in the immunological response and interact with IRAK in the Zhikong scallop (Chlamys farreri) - Jiwen Chen; Wei Chen; Yifan Qu; Xiaoxue Lin; Haikun Zhang; Jilv Ma; Jie Cui; Fengchen Liu; Zhongyi Chu; Yue Zhao; Yabin Wang; Yaqiong Liu; et al. (Aquaculture, 2026)

Nomilin ameliorates perfluorooctanoic acid (PFOA)-induced impairment of zebrafish (Danio rerio) ocular development and visual function through PIK3CA activation - Xing Liu; Mingzhu Xia; Xinyi Wu; Ruobing Chen; Yuting Peng; Yi Fan; Junjie Han; Yichun Zhao; Man Qu (Toxicology and Applied Pharmacology, 2026)

Application of functional graphene composites in heavy metal ion monitoring: A review - Han Zheng; Guangfei Qu; Keheng Pan; Junyan Li; Yuchen Shi; Changfei Guo; Wanyuan Du (Journal of Water Process Engineering, 2026)

Unveiling the black box: Multi-omics reveal how biochar supercharges synthetic biofilms for superior bioremediation - Bo Zhang; Xiaoying Hu; Lu Han; Zhen Guo; Yongqi Liu; Huiyao Li; Yuze He; Tianyu Liu; Qingyuan Pan; Yi Mu; Jianhua Qu; Hongqi Yu; et al. (Journal of Hazardous Materials, 2026)

Enhanced remediation of cadmium and lead in soil using two-step ball-milled micro zero-valent iron/phosphate/biochar composites: Synthesis, performance, and mechanisms - Jianhua Qu; Juncheng Wang; Lu Han; Zhaolin Du; Diogene Tuyiringire; Xu Liu; Siqi Wang; Hongan Chen; Ying Zhang (Journal of Environmental Sciences, 2026)

Assessing the feasibility and environmental benefits of electrifying construction machinery in Beijing, China - Huawei Yi; Yangyang Cui; Han Li; Guanghan Huang; Kaiyun Liu; Linzhen Qu; Jing Yan; Lei Nie; Yifeng Xue (Journal of Environmental Sciences, 2026)

Deciphering the butylated hydroxytoluene dissolution behavior in solid-liquid systems through coupled experimental and molecular dynamic simulation approaches - Xing Wu; Xiaowei Cheng; Shiyu Sun; Jixu Ni; Yuan Han; Mengwen Qu; Baoshu Liu; Hua Sun (Food Chemistry, 2026)

N-doped biochar as a promising peracetic acid activator for sulfamethoxazole removal: Performance and mechanism - Zhuoran Li; Lu Han; Ran Wang; Jiaxuan Yu; Siqi Wang; Kaige Li; Qun Jiang; Jie Liu; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2026)

Biochar-supported sulfurized nano-zero-valent iron for soil Cr(VI) immobilization: Mitigating migration and elucidating reduction mechanisms - Siqi Wang; Qinglu Zhou; Xue Han; Mengning Wang; Xuerui Liu; Qun Jiang; Tianqi Liu; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2026)

Hematite-facilitated anaerobic oxidation of organics: Novel strategy to alleviate bioclogging in constructed wetlands - Hao Qin; Yi Sun; Tao Liu; Xingchen Liu; Wenbo Nie; Han Qu; Jun Li; Yi Chen (Bioresource Technology, 2026)

Effects of roads on animals and mitigation measures in Asia - Haotong Su; Yun Wang; Qilin Li; Yangang Yang; Abudusaimaiti Maierdiyali; Shuangcheng Tao; Yaping Kong; Jiding Chen; Jiapeng Qu; Yongshun Han; Aili Kang; Shu Chen; et al. (Biological Conservation, 2026)

Nomilin mitigates OBS-induced developmental cardiotoxicity via the Nrf2 pathway - Xing Liu; Yi Fan; Ruobing Chen; Yuting Peng; Xinyi Wu; Mingzhu Xia; Yichun Zhao; Junjie Han; Man Qu (Aquatic Toxicology, 2026)

Mechanisms and Therapeutic Potential of Targeting Mitophagy in Neurodegenerative Diseases - Ya-Ning Wang; Xing Wang; Qin Huang; Yun Yang; Tao Wang; Xin-Hui Qu; Xiao-Jian Han (Molecular Neurobiology, 2026)

α-Synuclein Deletion Leads to Hyposmia: due to Defective Autophagy Induced by Abnormal PI3K/mTOR Signaling Pathway in Olfactory Bulb - Yuqing Shi; Huizhi Wang; Jing Chen; Jing Ren; Xiaohong Sun; Mingqin Qu; Tongfei Zhao; Chunlei Han; Junliang Yuan; Fangang Meng; Lingling Lu (Molecular Neurobiology, 2026)

A novel multiplex RPA/CRISPR-Cas12a integrated biosensor for on-site detection of high-risk HPV genotypes - Yuying Bao; Wei Ding; Ling Zhang; Wei Wang; Jia Liu; Yiting Qu; Liguo Zhu; Kairui Zhang; Guanxi Zhong; Rong Han; Qiang Shen; Bo Wang; et al. (Analytica Chimica Acta, 2026)

Contrasting geochemistry of apatite from the Jurassic W- and Sn-mineralized granites in the Qitianling field, Nanling Range, South China - Hongfei Di; Yong-Jun Shao; David Chew; Rui-Chang Tan; Han Zheng; Yong Liang; Wen-Jie Fang; Yi-Qu Xiong (Lithos, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

System design, control strategy development and performance comparison analysis for a novel air-liquid hybrid data center cooling system based on cold plates - Shengli Qu; Chuang Wang; Yishuang Liu; Yiwei Feng; Yaoxiang Han; Ziwen Xing (International Journal of Refrigeration, 2025)

A newly identified homolog of scallop caspase-3/7 plays a pivotal role in the immunological response and orchestrates the induction of apoptosis - Jie Cui; Dianzhi Yao; Haikun Zhang; Yifan Qu; Xiaoxue Lin; Yaqiong Liu; Yijing Han; Baoyu Huang; Xiaotong Wang (Fish & Shellfish Immunology, 2025)

Sprayable and scalable superhydrophobic passive daytime radiative cooling coating for sub-ambient temperature regulation - Chengjie Qu; Qingqing Lu; Bo Wang; Jinyue Song; Ziye Han; Xingxiang Ji; Zuankai Wang; Libin Liu (Energy and Buildings, 2025)

Radial growth of Pinus tabuliformis is affected by climatic factors and site conditions on a regional scale: An integrative analysis based on tree-ring width data - Yue Fan; Yujian Zhang; Siyu Liu; Chenhui Qu; Dongqing Han; Yanhong Liu (Dendrochronologia, 2025)

Nano-traps intervening in liquid-liquid phase separation-mediated scavenging of cell-free DNA for macrophage polarization remodeling - Shuyuan Qu; Yilong Zhao; Yue Han; Xiaojie Zhou; Yueqi Ni; Kun Tan; Xizhen Luo; Jing Zhang; Bin Gu; Jiaolong Wang; Chengcheng Yin; Qin Zhao; et al. (Chemical Engineering Journal, 2025)

Characterization of a novel biosurfactant from Alcanivorax dieselolei and its mechanism for enhanced oil recovery in low-permeability reservoirs - Shuyuan Deng; Bo Wang; Ruixue Qu; Yuxiao Han; Cenqian Zhang; Chenyue Wang; Jian Fu; Shanshan Sun; Hao Dong; Gongze Cao; Qing You; Yuehui She; et al. (Chemical Engineering Journal, 2025)

High-value upcycling of iron ore tailings into stable, non-toxic turquoise pigments for sustainable applications - Gaofeng Han; Zhongdan Shi; Wenqian Qu; Kailong Nie; Han Lu; Guangyan Tian (Waste Disposal & Sustainable Energy, 2025)

Immobilization of arsenic and antimony by silica-Fe (hydr)oxides composite: investigation of potential ecological effects on the soil microbial environment - Rui Xu; Yaxin Tian; Qian Li; Guangfei Qu; Lang Liao; Zhe Yin; Zhenguo Wu; Yuqi Han; Yan Zhang; Yongbin Yang; Dongbin Liu; Haiyan Yan; et al. (Environmental Geochemistry and Health, 2025)

How can environmental regulation and digital economy synergistically affect regional green innovation in China? Evidence based on double machine learning model - Han Yueming; Qu Shiyou (Environment, Development and Sustainability, 2025)

Research on the Characteristics of Deep and Medium-Level Geothermal Energy for Highway Ice Melting and Snow Removal - Taking the Jinan-Ningjin Expressway as an Example - Chuang-shan Wu; Zhao-di Han; Wen-xiang Yang; Jing-kai Qu; Zhao-feng Zheng; Fan-meng Kong; Kun Liang; Lin-zhi Lang (Applied Geophysics, 2025)

A cascading failure-based approach for assessing the resilience of urban stormwater networks - Wenli Liu; Han Gao; Yao Qu; Zihan Liu; Qian Wu (Sustainable Cities and Society, 2025)

Discovery of potent ATP citrate lyase inhibitors from Tripterygium wilfordii Hook. f.: a structural and bioactivity analysis - Boquan Qu; Jixia Wang; Yan Li; Tao Hou; Xiaonian Li; Dian Liu; Yang Han; Zhimou Guo; Fengbin Luo; Feifei Huang; Yunhui Zhu; Jiatao Feng; et al. (Phytochemistry, 2025)

Soil Water Accounting Network (SWAN): a novel neural network for modeling conceptual hydrological processes - Zheng Fang; Simin Qu; Ziheng Li; Qiongfang Li; Peng Shi; Yiqun Sun; Xiaoqiang Yang; Han Tang; Junfang Zhang; Zhengxian Zhu; Hongshi Wu; Weimin Bao (Journal of Hydrology, 2025)

Metagenomic analysis of bacterial fitness and plasmids carrying blaTEM-1 and virulence genes before and after cleaning and disinfection in pig slaughterhouses - Shanshan Chu; Yan Chen; Zhuoqun Xu; Jie Zhou; Keyu Li; Qi Zhang; Min Qian; Jianzhong Han; Daofeng Qu (Journal of Hazardous Materials, 2025)

Machine learning-assisted magnetic nanomotors for the identification and degradation of organic pollutants - Zhiqin Geng; Gang Wang; Bohan Gu; Bingxue Wen; Ziwen Wu; Rui Li; Linfen Duan; Yunsheng Shang; Weiqing Han; Kajia Wei; Lulu Qu (Journal of Hazardous Materials, 2025)

Spatiotemporal evolution patterns of mining-induced overburden damage based on microseismic event response analysis - Xiao Yang; Longqing Shi; Mei Qiu; Jin Han; Xingyue Qu; Song Fu (Journal of Applied Geophysics, 2025)

Unveiling molecular transformations and mechanisms of soil organic matter during thermal remediation across temperatures - Han Gao; Shang Gao; Lei Wang; Zhen Song; Xiaolei Qu; Minli Wang; Tao Long; Jinzhong Wan (Chemical Engineering Journal, 2025)

Synergistic defense mechanisms between soybean disease resistance genes and stomatal regulation - Jikai Li; Yanjun Li; Chunmei Luo; Shubo Zhou; Jemaa Essemine; Weibo Han; Mingnan Qu (Euphytica, 2025)

Straw return strategies for soil microbial quotient enhancement: Insights from DOM vertical distribution characteristics - Yuanchen Zhu; Wei Yang; Juanjuan Qu; Yue Jiang; Ying Zhao; Zhimin Wu; Jie Su; Xiaozeng Han; Wenxiu Zou (Agriculture, Ecosystems & Environment, 2025)

Utilizing UAV-based high-throughput phenotyping and machine learning to evaluate drought resistance in wheat germplasm - Xiaojing Zhu; Xin Liu; Qian Wu; Mengshi Liu; Xueli Hu; Hui Deng; Yun Zhang; Yunfeng Qu; Baoqi Wang; Xiaoman Gou; Qiongge Li; Changsheng Han; et al. (Computers and Electronics in Agriculture, 2025)

In-situ remediation efficiency and mechanism of tylosin contaminated soil with biochar immobilized degrading enzyme - Bo Zhang; Xiaoying Hu; Zhen Guo; Jianhua Qu; Yuze He; Lu Han; Juntong Kou; Hongqi Yu; Jiuxuan Lian; Ying Zhang (Journal of Hazardous Materials, 2025)

Durability and damage mechanisms of electrolytic manganese residue-based grouting materials for seepage prevention in solid waste landfills under simulated service environments - Conggan Xu; Ping Wang; Yifu Xu; Lijun Han; Saiou Fu; Yao Qu; Yongyong Chen; Weiyu Liu; Yaoyi Wang; Zhen Qi; Jing Nie; Xuewen Lei; et al. (Journal of Environmental Management, 2025)

Study on processability, hydration characteristics and solidification mechanism of hazardous elements of high-phosphorus solid waste paste backfill materials - Yandong Han; Lang Liu; Shishan Ruan; Mengbo Zhu; Bo Yu; Huisheng Qu; Chengcheng Shao; Tiantian Li (Journal of Environmental Chemical Engineering, 2025)

Functional characterization of a molluscan executioner caspase in apoptosis and innate immunity - Jie Cui; Zihao Zhang; Zhaoxi Zhang; Shuang Zhang; Haikun Zhang; Yifan Qu; Guoqing Yu; Yaqiong Liu; Yijing Han; Baoyu Huang; Xiaotong Wang (Fish & Shellfish Immunology, 2025)

Characterization of SiIκB confirms the existence of a conserved IκB–NF-κB regulatory mechanism in sea urchin Strongylocentrotus intermedius - Yifan Qu; Yan Gao; Jie Cui; Haikun Zhang; Fengchen Liu; Xiaoxue Lin; Zhongyi Chu; Yaqiong Liu; Yijing Han; Baoyu Huang; Xiaotong Wang (Fish & Shellfish Immunology, 2025)

Upper-critical-solution-temperature-type hydrogel smart window with wide temperature regulation for all weather privacy protection and energy saving - Hongzhi Liu; Chengjie Qu; Shuxian Song; Ziye Han; Xingxiang Ji; Ligang Gai; Libin Liu (Chemical Engineering Journal, 2025)

Rational design of triple-modal quercetin-iron nanocomplexes for preventing biofilm formation - Yangcui Qu; Zhuo Wang; Haitao Han; Jing Zhong; Jifa Liu; Jie Yang; Qian Yu; Guannan Wang (Chemical Engineering Journal, 2025)

Isolation and characterization of minor monoterpene glycosides from the roots of Paeonia lactiflora - Yongliang Ding; Dan Han; Qian Tang; Lijuan Wang; Zhongtang Qu (Biochemical Systematics and Ecology, 2025)

Nitrogen utilization in response to cadmium and abscisic acid in rice - Zhi-Jun Xu; Jia-Yi Qu; Meng Zhao; Jing Zhao; Wei-Chi Wang; Jia-Jun Huang; Jia-Shi Peng; Yun-Hua Xiao; Yong-Liang Han; Yan Peng; Bo-Han Liu; Zhen-Xie Yi; et al. (Plant and Soil, 2025)

Whole-Brain Monosynaptic Inputs to Parasubthalamic Calretinin Neurons in Mice - Han Guo; Mutian Zhang; Jie Huang; Haifeng Zhou; Min Zhang; Hongdan Wang; Xudong Xu; Xiaoyan Liu; Weimin Qu; Zhili Huang (Molecular Neurobiology, 2025)

Evolution and prediction of drought-flood abrupt alternation in mainland China using an improved index - Yiming Tong; Yu Chen; Yanping Qu; Virgílio A. Bento; Hongquan Song; Han Qiu; Wei Shui; Jingyu Zeng; Qianfeng Wang (Climate Dynamics, 2025)

Effects of North Atlantic summer marine heatwaves on Arctic sea ice freeze-up delay: modulation by atmospheric teleconnections - Xuan Zhou; Jie Su; Tianhao Zhao; Han Zhang; Zhifeng Qu (Climate Dynamics, 2025)

Development and multi-objective optimization of a solar-powered hybrid aerator for aquaculture - Zhi Qu; Changfeng Tian; Xuan Che; Mengxia Han; Yin Zhou (Aquacultural Engineering, 2025)

Small-molecule fluorescent probes for imaging intracellular amyloid toxicity induces ferroptosis via HClO fluctuation in Alzheimer's disease - Wenhui Ma; Bingbing Tang; Han Zhang; Yixin Qu; Jinfeng Luan; Kelong Wang; Wenbo Chen; Xijuan Wang; Xinran Liu; Hongyan Zhao; Haixia Li; Ming Luo; et al. (Analytica Chimica Acta, 2025)

CDIP-ChatGLM3: A dual-model approach integrating computer vision and language modeling for crop disease identification and prescription - Changqing Yan; Zeyun Liang; Han Cheng; Shuyang Li; Guangpeng Yang; Zhiwei Li; Ling Yin; Junjie Qu; Jing Wang; Genghong Wu; Qi Tian; Qiang Yu; et al. (Computers and Electronics in Agriculture, 2025)

Evaluating the influence of double-channel inclined spreading blades on the effect of fertiliser granule spreading: DEM modelling and simulations - Wenqi Zhou; Qu Lu; Yao Wang; Han Tang; Jinwu Wang; Yijia Wang; Xiaobo Sun (Biosystems Engineering, 2025)

Organic carbon deposition of a typical plateau deep lake across 150 years - Chungui Yu; Shanmeng Han; Xuetao Guo; Xiaofeng Cao; Gaoqi Duan; Jianfeng Peng; Huijuan Liu; Jiuhui Qu (Water Research, 2025)

Magic cube metamaterials - Zuntian Chu; Xinqi Cai; Ruichao Zhu; Tonghao Liu; Huiting Sun; Fan Wu; Tiefu Li; Yuxiang Jia; Yajuan Han; Shaobo Qu; Tiejun Cui; Jiafu Wang (Science Bulletin, 2025)

Efficient phosphate removal from wastewater using Mg/Fe-functionalized tea stalk biochar through green synthesis and bio-assembly method - Huiyao Li; Shuai Shi; lrina lvshina; Ziyan Wang; Jing Gui; Ruolai Wang; Chunyu Pan; Yiwen Ning; Jianhua Qu; Siyue Han; Ying Zhang (Process Safety and Environmental Protection, 2025)

Refining historical forest cover mapping and change analysis with time series algorithm-based samples transfer - Qianhuizi Guo; Ling Han; Liangzhi Li; Songjie Qu (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

A hybrid approach for identifying the seasonal variation of groundwater quality, source apportionment and health risk in a coastal area driven by natural and anthropogenic factors - Xin Xie; Houwei Ji; Qingchun Yang; Shuochao Bao; Chunmei Han; Wu Qu (Journal of Hazardous Materials, 2025)

Dielectrically optimized Ni/CeO2/CNT catalysts for low-power and stable microwave-assisted dry reforming of methane - Tingting Wang; Xiaojun Li; Fengjuan Liu; Bei Liu; Xinkang Peng; Zhiheng Wang; Ning Qu; Jie Kong; Zhenchen Tang; Feng Zeng; Han Lin; Xiaohua Lu; et al. (Chemical Engineering Journal, 2025)

Quality valuation and open fermentation process of polyhydroxyalkanoates production for the waste carbons biorefinery using Paracoccus sp. TOH as chassis - Leizhen Zhao; Lin Chen; Yuanxi Zhang; Jiexuan Han; Gaojie Sun; Jianhang Qu (Biomass and Bioenergy, 2025)

The design and calibration of a new differential calorimetric dedicated to nuclear heating measurements - Junxin Zhang; Tianchi Ma; Liang Zhang; Xingjie Peng; Guofeng Qu; Shuai Jin; Yixiong Sun; Jifeng Han; Guang Zhao (Annals of Nuclear Energy, 2025)

Isotopic signature for the fate of copper in laterites from Yunnan Province, southwest China - Bin Liang; Guilin Han; Rui Qu (Journal of Hazardous Materials, 2025)

How renewable energy policies cut greenhouse gas emissions: Insights from advanced data analysis techniques - Xinyue Gao; Yujie Ge; Jiansheng Qu; Jinyu Han; Tek Narayan Maraseni; Chunsen Liu; Kemin Huang; Li Xu; Dai Wang; Hengji Li (Journal of Environmental Management, 2025)

Accelerating enrichment of ARGs and MGEs with increasing ammonium removal during partial nitrification treating high-strength ammonia wastewater - Heng Yu; Weiyi Jia; Yuqiu Luo; Rong Zhang; Junkai Zhao; Cong Lu; Yue Dong; Shuo han; Bing Li; Chengtun Qu (Environmental Research, 2025)

Ultraviolet and visible dual-narrowband photomultiplication type organic photodetectors - Xingchao Zhao; Kaixuan Yang; Xiaoling Ma; Min Hun Jee; Hongfei Qu; Shuai Zhang; Yao Ma; Liang Shen; Guangcai Yuan; Qi Yao; Han Young Woo; Fujun Zhang (Chemical Engineering Journal, 2025)

Electrical percolation network based on nano-cellulose template for flexible hydrogel bioelectrode - Mengyao Guan; Zhiliang Han; Na Liu; Zhou Zhou; Xiangyang Qu; Tao Zhang; Shiyan Chen; Huaping Wang (Carbohydrate Polymers, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Fluoride ion-mediated differential coordination separation of Al (III) and Fe (III) for regeneration of low-aluminum, high-purity battery-grade iron phosphate - Fei Han; Yaohui Xie; Lin Qu; Zhenzhou Wang; Wei Zhang; Guang Yang; Huiqin Hu; Meiting Huang; Haoxuan Yu; Liming Yang; Xubiao Luo (Resources, Conservation and Recycling, 2025)

Self-enhanced multifunctional composite membranes based on metal-organic frameworks embedded with thymol nanoparticles for post-harvest preservation of fruits - Qi Chen; Dianpeng Han; Xiaoyu Qu; Wen Zhang; Yuan Peng; Shuang Li; Kang Qin; Shuyue Ren; Yu Wang; Huanying Zhou; Pei Zhao; Zijian Wu; et al. (Food Hydrocolloids, 2025)

Self-assembled multifunctional antimicrobial composite films of humidity-responsive pterostilbene@β-cyclodextrin inclusion complexes/carboxymethyl cellulose/zein for fruit preservation - Xiaoyu Qu; Dianpeng Han; Qi Chen; Guangna Ji; Yuan Peng; Shuang Li; Kang Qin; Shuyue Ren; Yu Wang; Huanying Zhou; Wenqiang Guan; Xinxuan Wang; et al. (Food Packaging and Shelf Life, 2025)

Tuning ligand defect in porphyrins metal-organic frameworks to boost electrochemiluminescence for sensitive detection of amyloid-β1-42 - Jinyan Li; Xiaoqi Pei; Rong Qu; Lei Liao; Wen Zhang; Zhen Wang; Gang Xie; Sanping Chen; Jing Han (Chemical Engineering Journal, 2025)

Thermal-enhanced deep removal of multiple impurities upon pH induction towards selective regeneration of high-purity iron phosphate - Yaohui Xie; Fen Zhang; Shuyu Xiang; Guang Yang; Lin Qu; Fei Han; Liang Xu; Liming Yang; Xubiao Luo (Chemical Engineering Journal, 2025)

Heavy metal contamination in fish and human health risks from lakes of a mega inter-basin water diversion - Wenxia Fan; Wentong Xia; Lian-Shin Lin; Han Liu; Xiao Qu; Wei Xin; Lizhou Tang; Yushun Chen (Chemosphere, 2025)

Metagenomic analysis reveals differences in antibiotic resistance and transmission risks across various poultry farming models - Yanru Huang; Shuaizhou Zong; Dingting Xu; Jiwei He; Yaru Zhang; Min Qian; Yuxing Li; Bohai Guo; Jianzhong Han; Daofeng Qu (Science of The Total Environment, 2025)

VAP27-1 interacts with KCS6 and CER2 to facilitate the biosynthesis of very- long-chain fatty acids - Haiyan Wang; Yifan Li; Qinyao Wang; Mengxia Wu; Ruiyuan Wang; Xinran Han; Lin Liu; Ting Liu; Chunmei Shi; Linlin Zhong; Hongyan Zhang; Yunjiang Cheng; et al. (Plant Science, 2025)

GAIN: A long-term maize germplasm innovation plan - Yang Wang; Peng Zhang; Yingjie Xiao; Hai-Jun Liu; Junqiang Ding; Yanzhi Qu; Jionghao Gao; Wenlong Li; Xiangyang Guo; Angui Wang; Wenqiang Li; Gengshen Chen; et al. (Molecular Plant, 2025)

Regional responses of ecosystem service security to land use changes and driving mechanisms: Insights from nearly 40 years of observations in Shaanxi, China - Songjie Qu; Ling Han; Liangzhi Li (Journal of Environmental Chemical Engineering, 2025)

Promotional activity of an uncharacterized protein Bm0979 on Nosema bombycis in silkworm, bombyx mori - Yujia Fang; Qiong Yu; Wenzhe Chen; Zhenghao Han; Qingsheng Qu; Zhenwei Jia; Shidong Jiang; Jie Cheng; Xudong Tang; Ping Qian (Journal of Asia-Pacific Entomology, 2025)

Hydrogen-substituted graphdiyne-facilitated polyamide membrane with improvement of water permeance - Wenjing Han; Yawen Tian; Zhou Qu; Chenyu Lai; Haoran Wang; Qianxi Yang; Hongwei Fan; Hong Meng (Desalination, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

HFNet: Semantic and Differential Heterogenous Fusion Network for Remote Sensing Image Change Detection - Yang Han; Jiayi Li; Yang Qu; Leiguang Wang; Xiaofeng Pan; Xin Huang (Journal of Geovisualization and Spatial Analysis, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Trends and magnitude of urban-rural food GHG inequalities over 33 years (1990–2022): Drivers, disparities, and future trends - Dai Wang; Jiansheng Qu; Tek Narayan Maraseni; Jinyu Han; Hengji Li; Li Xu; Jixing Tang; Dingye Wu (Journal of Cleaner Production, 2025)

FeP nanoparticles anchored on N-doped carbon as ORR/OER bifunctional catalyst and its application in Zn-air batteries - Yifei Su; Hongmei Du; Jingjing Xu; Jinsheng Zhao; Ningqiang Zhang; Bang Lu; Han Yan; Konggang Qu; Xianxi Zhang (Fuel, 2025)

Rutin Attenuates Distraction Spinal Cord Injury by Inhibiting Microglial Inflammation Through Downregulation of P38 MAPK/NF-κB/STAT3 Pathway - Junrui Jonathan Hai; Weishi Liang; Duan Sun; Peng Yin; Bo Han; Xianjun Qu (Molecular Neurobiology, 2025)

Hydrodynamic Study of a Fall Pipe Rock Dumping System - Mingjiu Zuo; Xinyi Zhou; Haiwen Tu; Zehui Liang; Yan Wei; Kai Xia; Haodi Zhu; Haibin Han; Jiayi Su; Fengzhong Qu (Journal of Marine Science and Engineering, 2025)
The fall pipe rock dumping technique is extensively employed to create protection embankments around submarine cables, mitigating distortion and breakage resulting from bottom scouring. During the rock dumping operation, intricate interactions among the pipeline, rocks, and water currents can affect the stability and efficiency of the fall pipe system. This research proposed a method employing the fluid–structure interaction to analyze the interactions between the pipeline, rocks, and water currents. The paper begins with the design of an innovative fall pipe rock dumping system and presents a theoretical analysis of the applied model testing approach. The simulation parameters were determined according to the geometric, Froude, and Strouhal similarity criteria. A thorough numerical analysis was performed to investigate the hydrodynamic properties of the rockfall pipeline under fluid–structure interaction. The research examined the settling of rocks during rockfall, along with the forces and movements associated with the deposition process. The results show that the rockfall pipeline experienced vortex-induced vibrations (VIVs) caused by ocean currents during operation. The maximum settling velocity of the rocks throughout the rockfall process reached 2.2 m/s, with a final stable velocity of 1.5 m/s. These simulation results offer critical insights for improving the design and functionality of the rockfall pipeline, thereby enhancing the protection of underwater infrastructure.

Posterior Probability-Based Symbol Detection Algorithm for CPM in Underwater Acoustic Channels - Ruigang Han; Ning Jia; Yufei Liu; Jianchun Huang; Suna Qu; Shengming Guo (Journal of Marine Science and Engineering, 2025)
The underwater acoustic (UWA) communication system is characterized by limited bandwidth, while continuous phase modulation (CPM) offers a constant envelope, improving power and spectrum utilization efficiency. However, severe inter-symbol interference (ISI) poses a significant challenge in CPM-based UWA communication. Traditional CPM frequency domain equalization (FDE) combined with simple phase detection neglects the inherent coding gain from CPM, leading to performance degradation. Although Viterbi detection provides high performance, its complexity makes it unsuitable for computationally constrained UWA systems. This paper proposes a symbol detection algorithm based on posterior probabilities combined with FDE (PS-FDE). PS-FDE improves CPM signal detection performance by effectively separating information, applying delay, and performing multiple rounds of information merging. Simulations using minimum shift keying (MSK) and Gaussian MSK signals demonstrate significant performance improvement in just a few iterations over UWA channels. A sea trial further validates the algorithm, showing a 15.83% reduction in bit error rate after three information mergings.

Comprehensive wheat lodging detection under different UAV heights using machine/deep learning models - Jianing Long; Zhao Zhang; Qu Zhang; Xiaohui Zhao; C. Igathinathane; Jianfei Xing; Chayan Kumer Saha; Wenyi Sheng; Han Li; Man Zhang (Computers and Electronics in Agriculture, 2025)

The characterization of a novel IRF8-like homolog and its role in the immune modulation of the sea urchin Strongylocentrotus intermedius - Baoyu Huang; Yifan Qu; Haikun Zhang; Jilv Ma; Jiwen Chen; Cui Jie; Fengchen Liu; Zhongyi Chu; Yaqiong Liu; Yijing Han; Xiaotong Wang; Wenhao Wang (Fish & Shellfish Immunology, 2025)

Metatranscriptomics reveals that plant tannins regulate the expression of intestinal antibiotic resistance genes in Qinghai voles (Neodon fuscus) - Shunqin Shi; Xueying Gan; Yuan Qian; Yiming Cao; Yu Wang; Chenwei Shi; Jie Bi; Qiaoling Yu; Qian Han; Jiapeng Qu; Huan Li (Environmental Research, 2025)

Research on the activity of dry-discharge coal-fired slag of different particle sizes and their performance as precursors of alkali-activated backfilling cementitious materials - Yandong Han; Lang Liu; Shishan Ruan; Chengcheng Shao; Mengbo Zhu; Huisheng Qu (Environmental Research, 2025)

Compression-torsion coupling auxetic tubular structures with enhanced stability - Jun Wen Shi; Wei Zhong Jiang; Yi Zhang; Yi Chao Qu; Xiao Ji; Jian Hao; Han Yan; Xin Ren (Engineering Structures, 2025)

Catalytic application of coal gasification slag-based materials: A review - Lei Han; Haijie Hu; Chengtun Qu; Jinling Li; Lanting Ma; Tao Yu (Chemical Engineering Journal, 2025)

Exosomal miR-27a-5p attenuates inflammation through Toll-like receptor 7 in foodborne Salmonella infections - Mingjuan Qu; Shengfa Su; Linlin Jiang; Xin Yu; Jianlong Zhang; Hongwei Zhu; Kexue Han; Xingxiao Zhang (Veterinary Microbiology, 2025)

miRNA-125a regulates porcine oocyte maturation in vitro by targeting ADAR - Yue Han; Ping Lu; Yongsheng Yu; Weiyu Gu; Chunyu Li; Yanqiu Lv; Xinglin Qu; Yuyang Zhang; Qinglong Xu; Shunfa Yao; Xuan Chen; Yi Jin (Theriogenology, 2025)

Recent advances in antibiotic removal using independent and coupled microbial fuel cells (MFCs): Mechanisms and cells (MFCs): Mechanisms and practical applications - Liye Liang; Yingzi Lin; Ruijun Ren; Qingjing Zhang; Jiangqi Qu; Yuanhao Liu; Zhe Han; Xin Sun (Journal of Water Process Engineering, 2025)

Smoke and NOx emission characteristics of in-use construction machinery base on substantial field measurement: A case study in Beijing, China - Huawei Yi; Yangyang Cui; Lijun Zhu; Yan Shen; Han Li; Guanghan Huang; Linzhen Qu; Dongdong Guo; Lei Nie; Yifeng Xue (Journal of Environmental Sciences, 2025)

Characterization of microplastic distribution, sources and potential ecological risk assessment of domestic sewage from ships - Na Lu; Qing Su; Yuxia Li; Ling Qu; Lingna Kong; Jiayi Cheng; Chao Wang; Jian Sun; Jianbo Han; Xiaomeng Wang (Environmental Research, 2025)

Forest thinning effects on soil carbon stocks and dynamics: Perspective of soil organic carbon sequestration rates - Qing Qu; Hongwei Xu; Lin Xu; Chengming You; Bo Tan; Han Li; Li Zhang; Lixia Wang; Sining Liu; Zhenfeng Xu; Sha Xue; Minggang Wang (CATENA, 2025)

Fish‐Finder: A robust small target detection method for aquaculture fish in low‐quality underwater images - Liang Liu; Junfeng Wu; Haiyan Zhao; Han Kong; Tao Zheng; Boyu Qu; Hong Yu (Journal of Fish Biology, 2025)
Underwater fish object detection serves as a pivotal research direction in marine biology, aquaculture management, and computer vision, yet it poses substantial challenges due to the complexity of underwater environments, occultations, and the small‐sized and frequently moving fish in aquaculture. Addressing these challenges, we propose a novel underwater fish object detection algorithm named Fish‐Finder. First, we engendered a structure titled “C2fBF,” utilizing the dual‐path routing attention protocol of BiFormer. The primary objective of this structure is to alleviate the perturbations induced by underwater intricacies during the phase of downsampling in the backbone network, thereby discerning and conserving finer contextual features. Subsequently, we co‐opted the RepGFPN method within our neck network—a distinctive approach that adeptly merges high‐level semantic constructs with low‐level spatial specifics, thus fortifying its multi‐scale detection prowess. Then, in an endeavor to diminish the sensitivity toward positional aberrations during the detection of diminutive aquatic creatures, we incorporated a novel bounding box regression loss function, the Wasserstein loss, to the existing CIoU. This innovative function gauges the congruity between the predicted bounding box Gaussian distribution and the reference bounding box Gaussian distribution. Finally, in regard to the dataset, we independently assembled a specific dataset termed “SmallFish.” This unique dataset, meticulously designed for the detection of small‐scale fish within intricate underwater settings, includes 5000 annotated images of small fish. Experimental results demonstrate that, compared to the state‐of‐the‐art detection methods, our proposed method improves the accuracy by and , and mean average precision (mAP) increases and in public dataset Kaggle‐Fish and our SmallFish dataset, respectively.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

DWAS-RL: A safety-efficiency balanced reinforcement learning approach for path planning of Unmanned Surface Vehicles in complex marine environments - Tianci Qu; Gang Xiong; Hub Ali; Xisong Dong; Yunjun Han; Zhen Shen; Fei-Yue Wang (Ocean Engineering, 2025)

Dissolved organic matter derived by microplastic: The release patterns, structure properties, composition, and the impact on rice - Mengli Chen; Shushan Liu; Fucheng Guo; Han Qu; Tao Liu; Ziwei Chen; Yi Chen (Journal of Environmental Chemical Engineering, 2025)

GN-GCN: Grid neighborhood-based graph convolutional network for spatio-temporal knowledge graph reasoning - Bing Han; Tengteng Qu; Jie Jiang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Engineering noble metal-free nickel catalysts for highly efficient liquid fuel production from waste polyolefins under mild conditions - Xinlei Han; Jiuxuan Zhang; Zhengyan Qu; Tuo Ji; Feng Zeng; Hong Jiang; Jun Huang; Zhenchen Tang; Weihong Xing; Rizhi Chen (Fuel, 2025)

Ultrasonic-assisted plasma-activated water extraction of polysaccharide from Hemerocallis citrina Baroni: Structural characterization and antioxidant mechanism in vitro - Tongliang Yang; Han Zhang; Yaqing Bian; Zihan Qu; Yifu Zhang; Shuhong Li; Guiyun Chen; Ye Chen (Food Chemistry, 2025)

Deciphering the mineral code of urinary stones: A first look at zinc isotopes - Ziyang Ding; Guilin Han; Yu Tian; Rui Qu; Jinke Liu; Di Wang; Ye Zhao (Environmental Pollution, 2025)

Protein-based supramolecular adhesive capable of on-demand adhesion and anti-adhesion for preventing undesired epidural tissue adhesion - Tong Li; Guang Wen; He Zhao; Yang Qu; Han Wu; Yingchuan Sun; Jianwu Zhao; Wen Li (Chemical Engineering Journal, 2025)

Associations of Exposure to 56 Serum Trace Elements with the Prevalence and Severity of Acute Myocardial Infarction: Omics, Mixture, and Mediation Analysis - Zhonghua Sun; Ying Xu; Ying Liu; Xinyu Tao; Ping Zhou; Han Feng; Yangyang Weng; Xiang Lu; Jun Wu; Yongyue Wei; Chen Qu; Zhengxia Liu (Biological Trace Element Research, 2025)

Effects of replacing soybean meal with fermented rapeseed meal in low-fish-meal feed on the growth, immunity, and gut microbiota of juvenile white shrimp, Litopenaeus vannamei - Yayu Qu; Fenglu Han; Yanbing Qiao; Xiaohui Shi; Hu Chen; Erchao Li (Aquaculture, 2025)

Enhanced preservation of cut rose flowers through bacterial nanocellulose produced from legume wastewater and fortified with Auricularia auricula polysaccharide - Yiran Yan; Yetong Feng; Tao Chen; Qiuling Shao; Nan Wu; Shuai Han; Jie Liu; Dingkang Wei; Yang Shen; Xinyu Zhang; Yang Li; Dehui Qu; et al. (Postharvest Biology and Technology, 2025)

NIR-driven GOx-like nanozyme-modified injectable thermoresponsive hydrogel for antibacterial therapy and bone regeneration in periodontitis - Changxing Qu; Tianying Luo; Ruxia Han; Dong Mo; Kun Shi; Xicheng Li; Zhongwu Bei; Meng Pan; Songtao Tan; Jun Liu; Zhiyong Qian (Chemical Engineering Journal, 2025)

Pyramid-Matrix-like buried interface construction for Boosting the photovoltaic performance of perovskite solar cells - Xin Luan; Ying Han; Mengyao Sun; Yingjie Wang; Le Zhang; Yuhuan Song; Fengyou Wang; Lin Fan; Xin Qu; Xiaoyan Liu; Lili Yang (Chemical Engineering Journal, 2025)

Synergistically networked 1D/2D/3D phase change composites with Ultra-Fast contactless thermal energy conversion and enhanced electromagnetic interference shielding performance - Xinpeng Hu; Bin Ai; Bingqing Quan; Zhanjin Shi; Zhigang Liu; Mengjie Sheng; Yang Ding; Han Yan; Yang Xiao; Gangchen Lu; Shuang Liu; Hao Wu; et al. (Chemical Engineering Journal, 2025)

Circular RNA-chimeric CeO2 nanoplatform maintains protective autophagy in macrophages for periodontitis - Yue Han; Liu Yang; Jing Zhang; Shuyuan Qu; Ziming Wang; Bin Gu; Yilong Zhao; Yufeng Zhang; Qin Zhao; Yaoting Ji (Chemical Engineering Journal, 2025)

Numerical Simulation and Experimental Study of a Small-Scale Vacuum Fish Pump - Changfeng Tian; Zhi Qu; Xuan Che; Mengxia Han; Yin Zhou; Fan Wu (Journal of Marine Science and Engineering, 2024)
The existing vacuum fish pump is too large and difficult to move, which is difficult to apply to small fishing vessels. However, the development of a small vacuum fish pump is not a single scaling of the existing vacuum fish pump but requires the support of relevant experiments and simulation theories. In this study, a vacuum fish pump suitable for small fishing vessels was developed. Firstly, a numerical model of the internal flow field during the vacuum fish pump’s working process was established using computational fluid dynamics (CFDs) and verified its effectiveness by physical experiments. It is found that the VOF model can well predict the variation of the volume fraction of the liquid phase in the whole calculation area with time during the suction or drainage process of the vacuum fish pump. Then, the internal flow field characteristics of the fish pump under different working conditions were simulated, and the rationality of the design of the fish pump was evaluated according to the numerical results. Finally, a separate physical experiment was carried out on grass carp, carp, crucian carp, silver carp, and bighead carp, respectively, and the capture efficiency and corresponding fish damage rate for different fish were analyzed. The experimental and numerical results show that the vacuum suction fish pump can achieve efficient and automatic suction and transport of live fish.

Research on the Influence of Shallow Buried Tunnel Crossing on the Stability of Overlying Frame Structure Building - Bo Wang; Suizi Jia; Mingyi Han; Jingkai Qu; Huimin Gong; Chao Lu; Ziming Qu (Journal of Marine Science and Engineering, 2024)
The land section of the Huangdao end of the Jiaozhou Bay Second Submarine Tunnel is extensively underlain by the Quaternary Loose Accumulation Layer. The tunnel passes through a weathered granite fracture zone with well-developed rock joints beneath the buildings. The tunnel excavation process significantly disturbs the buildings above, making them prone to settlement, cracking, and tilting. This research conducts numerical simulations of three tunnel excavation methods, and based on the results, compares the deformation behaviors of the ground surface and buildings under various conditions. The findings show that the double side-wall guide pit method has better adaptability in controlling surface settlement and building deformation than the vertical or curved CD method. Moreover, the removal of temporary supports significantly affects building settlement and tilt; this risk can be effectively reduced by controlling the stress relief ratio during the removal phase of the temporary supports in the tunnel. The significance of the study lies in the fact that by choosing an appropriate tunnel excavation support scheme, the disturbance impact on the overlying buildings can be minimized, and the construction safety and stability of the surrounding buildings can be guaranteed. The results of this study can provide initial guidance for constructing shallow-buried tunnels beneath existing buildings.

Responses of various organic carbon pools to elevated temperatures in soils - Yafeng Han; Chenchen Qu; Xiping Hu; Pan Sun; Jie Kang; Peng Cai; Xingmin Rong; Wenli Chen; Qiaoyun Huang (Science of The Total Environment, 2024)

Simultaneous algae-containing water treatment and power generation using floating iron-air electrocoagulation fuel cell - Xiaoyu Han; Jiangwei Lv; Yue Dong; Xin Zhao; Youpeng Qu; Junfeng Liu; Jie Zhang; Yujie Feng (Journal of Water Process Engineering, 2024)

Artemisia argyi leaf powder improves soil properties and recruits Sphingobium bacteria to promote the growth and yield of Pinellia ternata - Jinxin Li; Kaili Qu; Lu Wei; Hong Chen; Huixia Cai; Jingyi Zhang; Likun Mei; Bingsen Liu; Yifan Han; Yuhuan Miao; Dahui Liu (Journal of Environmental Management, 2024)

Scheelite as a microtextural and geochemical tracer of multistage ore-forming processes in skarn mineralization: A case study from the giant Xintianling W deposit, South China - Hongfei Di; Yong-Jun Shao; Yi-Qu Xiong; Han Zheng; Xiang Fang; Wenjie Fang (Gondwana Research, 2024)

A novel mutation in hERG gene associated with azithromycin-induced acquired long QT syndrome - Yun-Jiu Cheng; Yang Wu; Hui-Qiang Wei; Yi-Jian Liao; Li-Ping Qu; Yue-Han Pan; Li-Juan Liu; Wen-Tao Bi (Molecular Biology Reports, 2024)

Research progress in mechanisms and properties of nano-modified interface transition zone of Marine concrete - Yu Hu; Pan Chonggen; Shiyang Qu; Qunpeng Li; Sanqi Han (European Journal of Environmental and Civil Engineering, 2024)

ChatEV: Predicting electric vehicle charging demand as natural language processing - Haohao Qu; Han Li; Linlin You; Rui Zhu; Jinyue Yan; Paolo Santi; Carlo Ratti; Chau Yuen (Transportation Research Part D: Transport and Environment, 2024)

Visible-light-sensitive microrobots using H2O as fuel for highly efficient capture and precise detection of nanoplastics - Zhiqin Geng; Tangtang Deng; Bohan Gu; Xinting Qian; Rui Li; Linfen Duan; Junyang Li; Weiqing Han; Lulu Qu; Kajia Wei (Journal of Hazardous Materials, 2024)

Spatiotemporal analysis of the food-related carbon emissions of China: Regional heterogeneity and the urban‒rural divide - Jinyu Han; Jiansheng Qu; Tek Narayan Maraseni; Jingjing Zeng; Dai Wang; Yujie Ge; Dingye Wu (Journal of Environmental Management, 2024)

Curcumin is an efficacious therapeutic agent against Chilodonella uncinata via interaction with tubulin alpha chain as protein target - Wenjia Han; Kechen Yang; Xiaoping Tan; Longkun Gao; Shenye Qu; Gengrong Zhang; Wenqi Fan; Mingzhu Liu; Erlong Wang; Pengfei Li; Fei Ling; Gaoxue Wang; et al. (Fish & Shellfish Immunology, 2024)

A scallop IκB protein involved in innate immunity acts as a key regulator of NF-κB - Jiwen Chen; Yifan Qu; Juan Dong; Wenwen Xu; Yue Zhao; Jie Cui; Zhengjie Yu; Zihao Bao; Jilv Ma; Yijing Han; Yaqiong Liu; Baoyu Huang; et al. (Fish & Shellfish Immunology, 2024)

Unlocking maize yield potential through exploring canopy-root interactions with nature-based nutrient management - Yupeng Zhu; Junhao Wang; Yongjun Zhu; Han Lai; Ziren Qu; Jian Zhao; Dan Wei; Pu Wang; Qingfeng Meng (Field Crops Research, 2024)

Levels, enrichment characteristics, and health risks of halogenated and parent polycyclic aromatic hydrocarbons in traditional smoked pork - Zhe Wang; Mai Su; Yanli Zhang; Rongxin Peng; Yingxi Qu; Jiali Han; Jun Jin; Jicheng Hu (Environmental Pollution, 2024)

A sustainable and robust Janus film Inspired by the bird’s nest structure for efficient year-round outdoor thermal management - Yang Ding; Lida Wu; Xiang Lu; Yang Hu; Xinpeng Hu; Gangchen Lu; Shilong Liu; Zhigang Liu; Xiaolong Li; Yang Xiao; Han Yan; Zhimeng Lu; et al. (Chemical Engineering Journal, 2024)

Biomimetic Fe3+ metal-phenolic networks enable DNAzyme and Cas9 RNP delivery for synergistic tumor ferroptosis-immunotherapy - Chao Chen; Xueting Shen; Silin Shi; Yin Xu; Hongxiu Song; Lihua Qu; Shiyu Du; Yamei Gao; Xin Han (Chemical Engineering Journal, 2024)

Comparative Metabolomic Analysis Reveals the Impact of the Photoperiod on the Hepatopancreas of Chinese Grass Shrimp (Palaemonetes sinensis) - Duojia Qu; Chunyan Fu; Muyu Han; Yingdong Li (Fishes, 2024)
The photoperiod is a key environmental factor that in crustaceans influences development, feeding, and metabolism. In this study, liquid chromatography-tandem mass spectrometry was used to examine metabolic changes in Palaemonetes sinensis under different photoperiods. Our results showed that key metabolic pathways, such as linoleic acid metabolism, axon regeneration, pyrimidine metabolism, and cortisol synthesis, were significantly altered under both constant light (24L:0D) and constant darkness (0L:24D) compared with natural light conditions. The photoperiod notably affected the digestive and metabolic functions of P. sinensis. Most metabolic pathways were downregulated under full darkness and full light conditions, suggesting that inhibition of metabolism is a potential adaptive response. Furthermore, enzyme assays revealed significant variations in trypsin, lipase, and amylase activity across different photoperiods, highlighting the profound impact of light conditions on digestive functions. These findings suggest that extreme light conditions may negatively impact the metabolic and digestive functions of P. sinensis. This study provides new insights into the adaptive mechanisms of P. sinensis in response to photoperiod changes and offers valuable information for optimizing aquaculture practices to enhance the health and growth performance of this crustacean.

The construction of international wetland urban ecological security pattern coupled with MSPA and ESF - Zezhu Wei; Bin Dong; Wenyan Xu; Zhili Xu; Jianshen Qu; Hao Wang; Yuexia Han (Environmental Science and Pollution Research, 2024)

Abundance, characteristics and ecological risk assessment of microplastics in ship ballast water in ports around Liaodong Peninsula, China - Qing Su; Yuxia Li; Na Lu; Ling Qu; Xin Zhou; Yue Yu; Daping Lu; Junsong Han; Jianbo Han; Xiaotong Xu; Xiaomeng Wang (Marine Pollution Bulletin, 2024)

IKK2 modulates the innate immune response of Zhikong scallop (Chlamys farreri) to bacterial and viral stimuli through the MyD88-dependent Toll-like receptor signaling pathway - Lingling Li; Jie Cui; Yifan Qu; Jilv Ma; Jiwen Chen; Yue Zhao; Yijing Han; Yaqiong Liu; Baoyu Huang; Xiaotong Wang (Aquaculture, 2024)

Gut microbiome and antibiotic resistance genes in plateau model animal (Ochotona curzoniae) exhibit a relative stability under cold stress - Xianxian Mu; Shunqin Shi; Xueqian Hu; Xueying Gan; Qian Han; Qiaoling Yu; Jiapeng Qu; Huan Li (Journal of Hazardous Materials, 2024)

A facile electrospinning strategy to prepare cost-effective carbon fibers as a self-supporting anode for lithium-ion batteries - Xuefeng Han; Hui Guo; Baolin Xing; Hao Liang; Huihui Zeng; Weiwei Kang; Xiaoxiao Qu; Chuanxiang Zhang; Yijun Cao; Zhengfei Chen (Fuel, 2024)

Combined effects of microplastics and pharmaceutical and personal care products on algae: A critical review - Wei Yang; Hao Zhang; Shengfa Yang; Yi Xiao; Kailai Ye; Ruixu He; Yao Liu; Zuoyuan Hu; Wenshu Guo; Qin Zhang; Han Qu; Yufeng Mao (Environmental Pollution, 2024)

Improvement of methane reforming Ni-based catalyst stability by controlling the unsaturated coordination aluminum in metakaolinite - Libo Han; Jiadong Liu; Hui Yang; Hao Qu; Ruijue Hu; Haiquan Su; Yue Su; Lili Wan (Chemical Engineering Journal, 2024)

Vacancy engineering-induced spin polarization in heterogeneous phosphides by simple iron salt infiltration for efficient overall water splitting - Xuanning Qin; Zebin Yu; Zimu Zhang; Zuoyu Qin; Han Pang; Boge Zhang; Yanping Hou; Jun Huang; Ronghua Jiang; Jiayi Qu (Chemical Engineering Journal, 2024)

Enhanced passivation of lead and cadmium from contaminated farmland using biochar with tailored pore properties: Performance and mechanisms - Yue Tao; Shuqi Wei; Yang Xu; Lu Han; Fuxuan Bi; Siqi Wang; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2024)

Thalamic Nucleus Reuniens Glutamatergic Neurons Mediate Colorectal Visceral Pain in Mice via 5-HT2B Receptors - Di Li; Han Du; Shu-Ting Qu; Jing-Lai Wu; Yong-Chang Li; Qi-Ya Xu; Xia Chen; Xiao-Xuan Dai; Ji-Tian Xu; Qian Wang; Guang-Yin Xu (Neuroscience Bulletin, 2024)
Irritable bowel syndrome (IBS) is a common functional bowel disorder characterized by abdominal pain and visceral hypersensitivity. Reducing visceral hypersensitivity is the key to effectively relieving abdominal pain in IBS. Increasing evidence has confirmed that the thalamic nucleus reuniens (Re) and 5-hydroxytryptamine (5-HT) neurotransmitter system play an important role in the development of colorectal visceral pain, whereas the exact mechanisms remain largely unclear. In this study, we found that high expression of the 5-HT 2B receptors in the Re glutamatergic neurons promoted colorectal visceral pain. Specifically, we found that neonatal maternal deprivation (NMD) mice exhibited visceral hyperalgesia and enhanced spontaneous synaptic transmission in the Re brain region. Colorectal distension (CRD) stimulation induced a large amount of c-Fos expression in the Re brain region of NMD mice, predominantly in glutamatergic neurons. Furthermore, optogenetic manipulation of glutamatergic neuronal activity in the Re altered colorectal visceral pain responses in CON and NMD mice. In addition, we demonstrated that 5-HT 2B receptor expression on the Re glutamatergic neurons was upregulated and ultimately promoted colorectal visceral pain in NMD mice. These findings suggest a critical role of the 5HT 2B receptors on the Re glutamatergic neurons in the regulation of colorectal visceral pain.

Distribution characteristics and ecological risk analysis of microplastics in sediments and effluents related to offshore oil and gas activities in the Bohai Sea, China - Yuxia Li; Lingna Kong; Zhongxiu Li; Qing Su; Ling Qu; Xiaomeng Wang; Jianbo Han; Jiayi Cheng; Liang Wu; Naidong Zhang (Marine Pollution Bulletin, 2024)

Follicular fluid exosome-derived miR-339-5p enhances in vitro maturation of porcine oocytes via targeting SFPQ, a regulator of the ERK1/2 pathway - Yue Han; Junzheng Zhang; Wanfeng Liang; Yanqiu Lv; Xiaotong Luo; Chunyu Li; Xinglin Qu; Yuyang Zhang; Weiyu Gu; Xuan Chen; Yi Jin (Theriogenology, 2024)

Experimental investigation of slamming characteristics of stiffened elastic wedges with different deadrise angles: Part II–Structural response - Bingbing Han; Xue Qu; Luyao Zou; Shengnan Liu; Hui Li; Zhixian Chen (Ocean Engineering, 2024)

Molecular cloning and functional study of a Rel homologous gene in sea urchin Strongylocentrotus intermedius - Yifan Qu; Jie Cui; Jilv Ma; Jiwen Chen; Haikun Zhang; Yue Zhao; Zhengjie Yu; Zihao Bao; Yijing Han; Yaqiong Liu; Baoyu Huang; Xiaotong Wang (Fish & Shellfish Immunology, 2024)

Biphasic Mo-based catalysts with abundant pores and rich heterostructures for high-efficient production of hydrogen in both alkaline and acidic media - Guangyan Tian; Kefeng Zhang; Minghang Li; Kailong Nie; Bingxue Yao; Wenqian Qu; Yan Li; Gaofeng Han; Wenbo Wang (Chemical Engineering Journal, 2024)

“Butterfly-effect” nano-platforms for cascade immune amplification and tumor clearance through multi-modal therapy and immune sensitization - Haoyu Chen; Xiaoying Kong; Jiahui Yan; Tianyi Wang; Yaqian Lv; Fenglang Zhang; Danping Liu; Yingshan Qu; Jun Fu; Wei Han; Jinsheng Shi (Chemical Engineering Journal, 2024)

Novel overlapping constructed wetlands with water drops reoxygenation and lightweight fillers for decentralized wastewater treatment - Zhao Shuyuan; Li Guo; Shui Paipai; Nie Wenbo; Qu Han; Yan Jun; Li Hong; Wang Ruiling (Bioresource Technology, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

A newly identified scallop MyD88 interacts with TLR and functions in innate immunity - Baoyu Huang; Jilv Ma; Wenwen Xu; Jie Cui; Jiwen Chen; Yifan Qu; Yue Zhao; Yijing Han; Yaqiong Liu; Weizhong Wang; Xiaotong Wang (Fish & Shellfish Immunology, 2024)

Erythrocyte membrane-camouflaged nanodelivery strategy enhances gene editing efficiency of Cas9 RNP for boosting tumor senescence - Silin Shi; Chao Chen; Xueting Shen; Shiyu Du; Kunguo Liu; Yamei Gao; Lihua Qu; Jingjing Yang; Mengfan Tang; Xin Han (Chemical Engineering Journal, 2024)

Melanin-based duplex Cas9 ribonucleoprotein nanomedicine for synergistic phototherapy and immunotherapy - Liansheng Fan; Suchen Qu; Jing Qian; Gaoyu Shi; Qiqing Huang; Yanni Song; Yu Ji; Quli Fan; Xin Han (Chemical Engineering Journal, 2024)

Risk of Cardiovascular Disease Hospitalization After Common Psychiatric Disorders: Analyses of Disease Susceptibility and Progression Trajectory in the UK Biobank - Xin Han; Yu Zeng; Yanan Shang; Yao Hu; Can Hou; Huazhen Yang; Wenwen Chen; Zhiye Ying; Yajing Sun; Yuanyuan Qu; Junren Wang; Wei Zhang; et al. (Phenomics, 2024)
Whether associations between psychiatric disorders and hospitalization for cardiovascular diseases (CVDs) can be modified by disease susceptibility and the temporal pattern of these associated CVDs remain unknown. In our study, we conducted a matched cohort study of the UK Biobank including 44,430 patients with common psychiatric disorders (anxiety, depression, and stress-related disorders) between 1997 and 2019, together with 222,150 sex-, Townsend deprivation index-, and birth year- individually matched unexposed individuals. The hazard ratios (HRs) for CVD hospitalization associated with a prior psychiatric disorder were derived from Cox models, adjusted for multiple confounders. We then stratified the analyses by self-reported family history of CVD and CVD polygenic risk score (PRS) calculated based on summary statistics of independent genome-wide association studies. We further conducted disease trajectory analysis and visualized the temporal pattern of CVDs after common psychiatric disorders. During a mean follow-up of 12.28 years, we observed an elevated risk of CVD hospitalization among patients with psychiatric disorders, compared with matched unexposed individuals (hazard ratios [HRs] = 1.20, 95% confidence interval [CI]: 1.18–1.23), especially during the first six months of follow-up (1.72 [1.55–1.91]). The stratification analyses by family history of CVD and by CVD PRS obtained similar estimates between subgroups with different susceptibilities to CVD. We conducted trajectory analysis to visualize the temporal pattern of CVDs after common psychiatric disorders, identifying primary hypertension, acute myocardial infarction, and stroke as three main intermediate steps leading to further increased risk of other CVDs. In conclusion, the association between common psychiatric disorders and subsequent CVD hospitalization is not modified by predisposition to CVD. Hypertension, acute myocardial infarction, and stroke are three initial CVDs linking psychiatric disorders to other CVD sequelae, highlighting a need of timely intervention on these targets to prevent further CVD sequelae among all individuals with common psychiatric disorders.

Disinfectant-induced ammonia oxidation disruption in microbial N-cycling process in aquatic ecosystem after the COVID-19 outbreak - Lutong Yang; Ping Han; Qiaojuan Wang; Hui Lin; Donglin Wang; Jie Mao; Weixiao Qi; Yaohui Bai; Jiuhui Qu (Water Research, 2024)

PM2.5 exposure inhibits osteoblast differentiation by increasing the ubiquitination and degradation of Smad4 - Jiatao Yang; Chunqing Han; Junxing Ye; Xiping Hu; Ruijian Wang; Jin Shen; Longfei Li; Guoqin Hu; Xian Shi; Zhongtang Jia; Xiuxia Qu; Huanliang Liu; et al. (Toxicology Letters, 2024)

Multi-elements linear discriminant analysis of herbaceous and woody plants in southwest china karst region using orthogonal partial least squares model - Yuqing Zhao; Guilin Han; Rui Qu; Qian Zhang (Plant Ecology, 2024)

Liner Schedule Design under Port Congestion: A Container Handling Efficiency Selection Mechanism - Haibin Qu; Xudong Wang; Lingpeng Meng; Chuanfeng Han (Journal of Marine Science and Engineering, 2024)
Port congestion significantly impacts the reliability of container ship schedules. However, the existing research often treats vessel time in port as a random variable, failing to systematically consider the complex impact of port congestion on ship schedules. This study addresses the issue of container ship schedule design under port congestion. Vessel waiting times in ports are predicted and quantified by queueing theory, along with information on vessel schedules, cargo handling volumes, and available port operating time windows. We propose a mechanism for selecting container handling efficiencies for arriving vessels, thereby determining their in-port handling times. By jointly considering the uncertainty of vessel waiting and handling times in port, we establish a mixed-integer nonlinear programming model aimed at minimizing the total cost of liner transportation services. We linearize the model and solve it using CPLEX, ultimately devising a robust ship schedule. A simulation analysis is conducted on a real liner shipping route from Asia to the Mediterranean, revealing that extreme weather events, geopolitical conflicts, and other factors can lead to severe congestion at certain ports, necessitating timely adjustments to vessel schedules by shipping companies. Moreover, such events can impact the marine fuel market, prompting shipping companies to adopt strategies such as increasing vessel numbers and reducing vessel speeds in response to high fuel prices. Additionally, the container handling efficiency selection mechanism based on information sharing enables shipping companies to flexibly design liner schedules, balancing the economic costs and service reliability of container liner transportation.

Bioaccessibility and human health risks of arsenic from geological origin in lateritic red soil on construction land - Lu-Yao Ding; Guang-Yong Tang; Ming-Zhu Chen; Fo-Peng Wang; Jun-Feng Wang; Han-Jie Ye; Qu-Sheng Li (Chemosphere, 2024)

Significant influence of urban human activities and marine input on rainwater chemistry in a coastal large city, China - Jie Zeng; Guilin Han; Qixin Wu; Rui Qu; Qing Ma; Jingwen Chen; Shijun Mao; Xin Ge; Zhong-Jun Wang; Zhiheng Ma (Water Research, 2024)

Different oxygen affinities of methanotrophs and Comammox Nitrospira inform an electrically induced symbiosis for nitrogen loss - Hao Wu; Wen-Bo Nie; Xin Tan; Guo-Jun Xie; Han Qu; Xin Zhang; Zhihao Xian; Jingyi Dai; Chun Yang; Yi Chen (Water Research, 2024)

Life-Cycle analysis of economic and environmental effects for electric bus transit systems - Mingyang Pei; Yi Hu; Weiji Han; Xiaobo Qu; Changfu Zou (Transportation Research Part D: Transport and Environment, 2024)

Overcoming research challenges: In vitro cultivation of Ameson portunus (Phylum Microsporidia) - Ming Fu; Hongnan Qu; Yongliang Wang; Jingyu Guan; Tian Xia; Kai Zheng; Liyuan Tang; Chunxue Zhou; Huaiyu Zhou; Wei Cong; Jinyong Zhang; Bing Han (Journal of Invertebrate Pathology, 2024)

Preparation of polystyrene and silane-modified nano-silica superhydrophobic and superoleophilic three-dimensional composite fiber membranes for efficient oil absorption and oil-water separation - Zhihui Dong; Nan Qu; Qiushi Jiang; Tong Zhang; Zhaolian Han; Jiapeng Li; Ruiqi Zhang; Zhiqiang Cheng (Journal of Environmental Chemical Engineering, 2024)

Dextral shear initiation of the Kangguer Shear Zone in the East Tianshan: Constraints from a “porphyroclast” system - Bo Liu; Zhengle Chen; Mengmeng Qu; Feng Yuan; Awei Mabi; Mingqiang Sheng; Jing Liu; Fengbin Han; Wengao Zhang; Hailong Huo (Journal of Asian Earth Sciences, 2024)

Polysaccharides from Auricularia cornea var. Li.: Structural alterations during in vitro digestion and its potent immunomodulatory properties on macrophages - Nan Lin; Minmeng Li; Zixuan Han; Xiaojuan Liu; Jialin Qu; Xinhui Wang; Xuchang Duan; Caian He (Food Bioscience, 2024)

Molecular confirmation and functional study of signal transducer and activator of transcription genes in the Pacific oyster Crassostrea gigas - Jilv Ma; Jie Cui; Yifan Qu; Jiwen Chen; Yue Zhao; Yijing Han; Yaqiong Liu; Baoyu Huang; Xiaotong Wang (Fish & Shellfish Immunology, 2024)

Condition assessment of stay cables using normalized sequence of vehicle-induced cable force peaks of stay cables on same side - Jin-Xin Li; Chun-Xu Qu; Ting-Hua Yi; Hong-Nan Li; Qiang Han (Engineering Structures, 2024)

Pollution characteristics, source apportionment, and health risk assessment of PM10 and PM2.5 in rooftop and kerbside environment of Lanzhou, NW China - Chen-ming Gu; Bo Wang; Qu Chen; Xiao-han Sun; Mei Zhang (Environmental Science and Pollution Research, 2024)

Solution-processed nanoporous and faceted CuO electrocatalyst for enhanced solar-to-hydrogen and nitrate-to-ammonia production - Runfa Tan; Min Je Kang; Li Qu; Sung Won Hwang; Seo Yeong Hong; Yoo Jae Jeong; Hyun Soo Han; Dong Hoe Kim; Sangwook Lee; In Sun Cho (Journal of Water Process Engineering, 2024)

Fabrication and characterization of sodium alginate/blueberry anthocyanins/hinokitiol loaded ZIF-8 nanoparticles composite films with antibacterial activity for monitoring pork freshness - Bohai Guo; Yun Sun; Qiuyue Guan; Zheng Luo; Lian Zhou; Zhenlan Xu; Jianzhong Han; Daofeng Qu (Food Chemistry, 2024)

Ball-milled sepiolite/phosphate rock for simultaneous remediation of cadmium-contaminated farmland and alleviation of phosphorus deficiency symptoms in pepper - Jianhua Qu; Yuhui Li; Hebang Sun; Ruixin Liu; Yue Han; Fuxuan Bi; Hongli Fan; Guosheng Zhang; Yupeng Zhang; Yifan Wang; Weidong Cao; Ying Zhang (Chemical Engineering Journal, 2024)

Key factors controlling nitrogen transformation and efflux at the sediment–water interface: a comparative study from different trophic reservoirs - Jie Ren; Guilin Han; Xiaolong Liu; Rui Qu; Ziyang Ding (Journal of Soils and Sediments, 2024)

3-D coseismic displacement mapping of the 2015 Mw7.8 Gorkha earthquake using multi-viewed InSAR - Han Chen; Chunyan Qu; Dezheng Zhao; Xinjian Shan; Chao Ma; Wenyu Gong; Lei Zhao; Luca Dal Zilio (Tectonophysics, 2024)

Direct borylation of alcohol over bifunctional copper/zeolite catalyst - Huifen Han; Jie Gao; Xiaoshan Qu; Yumeng Sun; Tong Xu; Heng Yang; Feng Chen (Sustainable Chemistry and Pharmacy, 2024)

Resources recovery from coal gasification residue by combined hydrocyclone and vibrating screen and characterization of separated products - Ningning Zhang; Fuqiang Zhao; Rui Han; Zhen Li; Zhanglei Zhu; Jinzhou Qu; Hong Wang; Anning Zhou (Process Safety and Environmental Protection, 2024)

A comprehensive assessment indicator of the water-energy-food nexus system based on the material consumption relationship - Lingang Hao; Jingjie Yu; Ping Wang; Chunhui Han; Boris Gojenko; Bo Qu; Enhui Jiang; Sherzod Muminov (Journal of Hydrology, 2024)

Target setting and performance analysis: Promoting e-waste collection in China under the collection target responsibility models - Hailei Yin; Ying Qu; Han Jia (Journal of Environmental Management, 2024)

High contributions of fossil fuel sources to char-EC/soot-EC at a high-altitude site: Direct radiative effects and transport pathway - Huikun Liu; Qiyuan Wang; Yao Qu; Jie Tian; Li Li; Nan Ma; Yaqing Zhou; WeiKang Ran; Hui Su; Yongming Han; Giulia Pavese; Junji Cao (Fuel, 2024)

The impacts of regional transport on anthropogenic source contributions of PM2.5 in a basin city, China - Huikun Liu; Qiyuan Wang; Peng Wei; Qian Zhang; Yao Qu; Yong Zhang; Jie Tian; Hongmei Xu; Ningning Zhang; Zhenxing Shen; Hui Su; Yongming Han; et al. (Science of The Total Environment, 2024)

Biodegradation of atrazine with biochar-mediated functional bacterial biofilm: Construction, characterization and mechanisms - Bo Zhang; Jingdan Zhang; Yuping Wang; Jianhua Qu; Zhao Jiang; Xu Zhang; Yue Tao; Yifan Wang; Zhonghui Kang; Songting Han; Jingyi Zhang; Ying Zhang (Journal of Hazardous Materials, 2024)

Exploration of natural processes and anthropogenic inputs by Zn isotopes in suspended particulate matter: A case study from the Lancang River in Southwest China - Yang Tang; Guilin Han; Rui Qu; Jinke Liu; Man Liu (Environmental Pollution, 2024)

Responses of soil aggregate stability to carbon and nitrogen under precipitation gradients in a desert steppe - Yuanyuan Cui; Dongjie Hou; Zhongwu Wang; Jing Wang; Zhiqiang Qu; Yunbo Wang; Guodong Han; Zhiguo Li; Haiyan Ren; Haiming Wang (Journal of Soils and Sediments, 2024)

Using solid phase adsorption toxin tracking and extended local similarity analysis to monitor lipophilic shellfish toxins in a mussel culture ranch in the Yangtze River Estuary - Wenguang Zhang; Zi Ye; Peipei Qu; Dongmei Li; Han Gao; Yubo Liang; Zhiguo He; Mengmeng Tong (Marine Pollution Bulletin, 2024)

Effect of corn stalks on coal catalytic hydrogasification in a pressurized fluidized bed for manufacturing CH4 - Shuai Yan; Jun Feng; Zihong Xia; Yingying Huang; Fengshuang Han; Xuan Qu; Jicheng Bi (Fuel, 2024)

Maternal serum neonicotinoids during early-mid pregnancy and congenital heart diseases in offspring: An exploratory study - Yanji Qu; Adela Jing Li; Xiaoqing Liu; Shao Lin; Michael S. Bloom; Ximeng Wang; Xiaohong Li; Hui Wang; Fengzhen Han; Xiangmin Gao; Yong Wu; Kaiqin Huang; et al. (Environmental Pollution, 2024)

Integrated municipal wastewater treatment and lipid accumulation by a self-flocculating/floating microalga Limnothrix sp. - Song-Fang Han; Wenbiao Jin; Fanqi Qu; Dieter Hanelt; Abdelfatah Abomohra (Bioresource Technology, 2024)

Magnetic characteristics of atmospheric particulate matter and its indication of atmospheric pollution during winter in Lanzhou, NW China - Bo Wang; Chen-ming Gu; Qu Chen; Mei Zhang; Xiao-han Sun; Jia Jia (Atmospheric Environment, 2024)

Potentially toxic elements in rainwater during extreme rainfall period in the megacity Beijing: Variations, sources, and reuse potential - Jie Zeng; Guilin Han; Shitong Zhang; Qian Zhang; Rui Qu (Atmospheric Environment, 2024)

Soil respiration and its determinants under simulated precipitation in a desert steppe - Yuanyuan Cui; Dongjie Hou; Zhongwu Wang; Jing Wang; Zhiqiang Qu; Yunbo Wang; Guodong Han; Zhiguo Li; Haiyan Ren; Haiming Wang (Journal of Soils and Sediments, 2024)

Urbanization reduces fish taxonomic and functional diversity while increases phylogenetic diversity in subtropical rivers - Bo Yang; Xiao Qu; Han Liu; Min Yang; Wei Xin; Weiming Wang; Yushun Chen (Science of The Total Environment, 2024)

Selenium-molybdenum interactions reduce chromium toxicity in Nicotiana tabacum L. by promoting chromium chelation on the cell wall - Lili Qu; Zicheng Xu; Wuxing Huang; Dan Han; Bingjun Dang; Xiaohan Ma; Yizan Liu; Jiayang Xu; Wei Jia (Journal of Hazardous Materials, 2024)

Biodegradation of poly(ethylene terephthalate) through PETase surface-display: From function to structure - Wei Han; Jun Zhang; Qi Chen; Yuzhu Xie; Meng Zhang; Jianhua Qu; Yuanji Tan; Yiran Diao; Yixuan Wang; Ying Zhang (Journal of Hazardous Materials, 2024)

New tracer for anthropogenic pollution in the atmosphere: Stable potassium isotopes in rainwater - Rui Qu; Guilin Han; Jie Zeng (Journal of Cleaner Production, 2024)

The mechanism of a submerged aquatic plant to various size of micro-nano plastics stress in ecological constructed wetland - Siyu Zhang; Lurui Han; Jianfeng Peng; Ruiping Liu; Huijuan Liu; Jiuhui Qu (Chemical Engineering Journal, 2024)

Climate match is key to predict range expansion of the world's worst invasive terrestrial vertebrates - Yuanbao Du; Xuyu Wang; Sadia Ashraf; Weishan Tu; Yonghong Xi; Ruina Cui; Shengnan Chen; Jiajie Yu; Lixia Han; Shimin Gu; Yanhua Qu; Xuan Liu (Global Change Biology, 2024)
Understanding the determinants of the range expansion of invasive alien species is crucial for developing effective prevention and control strategies. Nevertheless, we still lack a global picture of the potential factors influencing the invaded range expansion across taxonomic groups, especially for the world's worst invaders with high ecological and economic impacts. Here, by extensively collecting data on 363 distributional ranges of 19 of world's worst invasive terrestrial vertebrates across 135 invaded administrative jurisdictions, we observed remarkable variations in the range expansion across species and taxonomic groups. After controlling for taxonomic and geographic pseudoreplicates, model averaging analyses based on generalized additive mixed‐effect models showed that species in invaded regions having climates more similar to those of their native ranges tended to undergo a larger range expansion. In addition, as proxies of propagule pressure and human‐assisted transportation, the number of introduction events and the road network density were also important predictors facilitating the range expansion. Further variance partitioning analyses validated the predominant role of climate match in explaining the range expansion. Our study demonstrated that regions with similar climates to their native ranges could still be prioritized to prevent the spread of invasive species under the sustained global change.

CTAB-modified peanut husk pre-treated with KMnO4 as an eco-friendly adsorbent for the uptake of Congo red in solution: adsorption and mechanism study - Aaron Albert Aryee; Runping Han; Lingbo Qu (Environmental Science and Pollution Research, 2023)

Iron isotope fractionation of redox and geochemical cycling in the typical Gleysols in Mun River Basin, Northeast Thailand - Qian Zhang; Guilin Han; Jie Zeng; Lingqing Wang; Guangyou Zhu; Man Liu; Bin Liang; Rui Qu; Xiaoqiang Li; Shitong Zhang (Science of The Total Environment, 2023)

Preparation of zirconium functionalized magnetic peanut husk crosslinked with polyethyleneimine and its application for the adsorption of phosphates in aqueous solution - Aaron Albert Aryee; Runping Han; Lingbo Qu (Journal of Environmental Chemical Engineering, 2023)

Organic pollutants removal from aqueous solutions using metal-organic frameworks (MOFs) as adsorbents: A review - Lixin Li; Jiazhen Han; Xiaohui Huang; Shan Qiu; Xihan Liu; Lilai Liu; Mengjie Zhao; Jiwei Qu; Jinlong Zou; Jun Zhang (Journal of Environmental Chemical Engineering, 2023)

Metagenomics reveals the self-recovery and risk of antibiotic resistomes during carcass decomposition of wild mammals - Qiaoling Yu; Qian Han; Tongtong Li; Yongping Kou; Xiao Zhang; Yansu Wang; Guoliang Li; Huakun Zhou; Jiapeng Qu; Huan Li (Environmental Research, 2023)

Bacterial cellulose-based film with self-floating hierarchical porous structure for efficient solar-driven interfacial evaporation - Mengtian Jin; Xiangyang Qu; Jing Li; Lili Deng; Zhiliang Han; Shiyan Chen; Huaping Wang (Carbohydrate Polymers, 2023)

Performance of 18F-DCFPyL PET/CT in Primary Prostate Cancer Diagnosis, Gleason Grading and D'Amico Classification: A Radiomics-Based Study - Yuekai Li; Fengcai Li; Shaoli Han; Jing Ning; Peng Su; Jianfeng Liu; Lili Qu; Shuai Huang; Shiwei Wang; Xin Li; Xiang Li (Phenomics, 2023)

Parerythrobacter aestuarii sp. nov., Isolated from Seawater in the Tidal Region of Taizhou - Han Dong; Ren-Zhuang Han; Yu Zhang; Maripat Xamxidin; Peng Zhou; Cong Sun; Wu Qu; Lin Xu (Current Microbiology, 2023)

Fish Recognition in the Underwater Environment Using an Improved ArcFace Loss for Precision Aquaculture - Liang Liu; Junfeng Wu; Tao Zheng; Haiyan Zhao; Han Kong; Boyu Qu; Hong Yu (Fishes, 2023)
Accurate fish individual recognition is one of the critical technologies for large-scale fishery farming when trying to achieve accurate, green farming and sustainable development. It is an essential link for aquaculture to move toward automation and intelligence. However, existing fish individual data collection methods cannot cope with the interference of light, blur, and pose in the natural underwater environment, which makes the captured fish individual images of poor quality. These low-quality images can cause significant interference with the training of recognition networks. In order to solve the above problems, this paper proposes an underwater fish individual recognition method (FishFace) that combines data quality assessment and loss weighting. First, we introduce the Gem pooing and quality evaluation module, which is based on EfficientNet. This module is an improved fish recognition network that can evaluate the quality of fish images well, and it does not need additional labels; second, we propose a new loss function, FishFace Loss, which will weigh the loss according to the quality of the image so that the model focuses more on recognizable fish images, and less on images that are difficult to recognize. Finally, we collect a dataset for fish individual recognition (WideFish), which contains and annotates 5000 images of 300 fish. The experimental results show that, compared with the state-of-the-art individual recognition methods, Rank1 accuracy is improved by 2.60% and 3.12% on the public dataset DlouFish and the proposed WideFish dataset, respectively.

Black carbon, soil organic matter molecular signatures under different land uses in Shenyang, China and relationship with PAHs - Han Gao; Huixin Li; Jiaqi Shi; Jianbo Huang; Jing Wei; Xiaolei Qu; Tao Long (Chemosphere, 2023)

Subchronic exposure to di-(2-ethylhexyl) phthalate (DEHP) elicits blood–brain barrier dysfunction and neuroinflammation in male C57BL/6J mice - Wen-qiang Ren; Nuo Liu; Yan Shen; Xian-yan Wang; Qiong Zhou; Chen Rui; Xiao-han Yang; Sheng-long Cao; Ling-yu Li; Yán Wāng; Qu-nan Wang (Toxicology, 2023)

The characteristics of rare earth elements in the main water filling sources of Sunan mining area - Xingyue Qu; Mei Qiu; Longqing Shi; Jin Han (Journal of Cleaner Production, 2023)

High-value utilization of Cr-containing sludge: Eco-friendly and ultra-low-cost electrocatalyst for efficient OER in alkaline media from Cr-containing sludge - Qiangqiang Lu; Qingxin Han; Xuechuan Wang; Chao Wei; Xiaoyu Guan; Chun Qu; Ji Li (Journal of Environmental Management, 2023)

Nitrogen evolution during membrane-covered aerobic composting: Interconversion between nitrogen forms and migration pathways - Jinpeng Xiong; Qianting Zhuo; Ya Su; Huiwen Qu; Xueqin He; Lujia Han; Guangqun Huang (Journal of Environmental Management, 2023)

Effect of low molecular weight organic acids on the lead and chromium release from widely-used lead chromate pigments under sunlight irradiation - Han Gao; Huixin Li; Xinwei Zhou; Jing Wei; Xiaolei Qu; Tao Long (Environmental Pollution, 2023)

Contrasting riverine K and Li isotope signatures during silicate weathering in the southeastern Tibetan Plateau - Xiaoqiang Li; Guilin Han; Qian Zhang; Jinke Liu; Rui Qu (Earth and Planetary Science Letters, 2023)

Comparative Analysis of Hepatopancreas RNA-Seq of Juvenile Grass Carp (Ctenopharyngodon idella) Fed Different Starch Diets - Jingjing Zhang; Xue Guo; Zhen Han; Letian Qu; Teng Xia; Xiangning Chen; Jianhe Xu; Zhujin Ding; Chaoqing Wei; Hanliang Cheng (Fishes, 2023)
This study aimed to explore the effects of different starch source diets on the growth performance and hepatopancreas RNA-seq of grass carp. Juvenile grass carp (initial body weight of 39.4 ± 1.6 g) were fed diets containing 25% corn (CO), potato (PO), and wheat (WH) starch for 8 weeks, respectively. The weight gain ratio (WGR) was significantly lower, whereas the visceral somatic index (VSI) and feed conversion ratio (FCR) were significantly higher in the CO group than those in the PO and WH groups. These indicators did not significantly differ between the PO and WH groups. Hepatopancreas RNA-seq analysis showed that 536, 514, and 647 differentially expressed genes (DEGs) were screened out in the comparisons of PO vs. WH, PO vs. CO, and CO vs. WH. The DEGs were mainly enriched in the several known pathways involved in steroid biosynthesis, cell cycle, fatty acid metabolism, and fat digestion and absorption according to Kyoto encyclopedia of genes and genomes (KEGG) pathway enrichment analysis. The major DEGs related to lipid and carbohydrate metabolism were analyzed, in which lipogenesis-related DEGs (fasn, acc1, scd1, elovl6, and me1), fat digestion and absorption-related DEGs (fabp7, apoa1, apoa4, and pla2), and glycometabolism-related DEGs (gk, g6pd, and pepck) were down-regulated in the PO group compared with those in the CO and WH groups. Conversely, steroid synthesis-related DEGs (hmgcs, fdft1, sqle, lss, cyp51, msmo1, nsdhl, ugt, cyp1b1, and cyp7a1) were up-regulated in the PO group. These results indicate that the long-term PO ingestion could modulate hepatic lipid metabolism by reducing fatty acid biosynthesis and increasing bile acid biosynthesis. PO may be healthier in contrast to CO alone, which may not be suitable as a starch source in grass carp diet.

Math-data integrated prediction model for ship maneuvering motion - Qi Dong; Ning Wang; Jialin Song; Lizhu Hao; Shaoman Liu; Bing Han; Kai Qu (Ocean Engineering, 2023)

Extracellular vesicles in porcine seminal plasma maintain sperm function by reducing Lyso-PC - Xuan Chen; Yinghai Jin; Yanqiu Lv; Yue Han; Xinglin Qu; Yuyang Zhang; Chunyu Li; Yi Jin (Livestock Science, 2023)

A magnetic biomass/MOF composite as a functional material for the oxidative removal of tetracycline: Degradation mechanism and toxicity study - Aaron Albert Aryee; Yuting Ma; Junli Wang; Runping Han; Lingbo Qu (Journal of Environmental Chemical Engineering, 2023)

Temporal-spatial distributions of road silt loadings and fugitive road dust emissions in Beijing from 2019 to 2020 - Haibin Wang; Lihui Han; Tingting Li; Song Qu; Yuncheng Zhao; Shoubin Fan; Tong Chen; Haoran Cui; Junfang Liu (Journal of Environmental Sciences, 2023)

Characterization and fitness cost analysis of two plasmids carrying different subtypes of bla in aquaculture farming - Yaru Zhang; Dingting Xu; Ze He; Jianzhong Han; Daofeng Qu (Food Microbiology, 2023)

CuO2-assisting-Zn single atom hybrid nanozymes for biofilm-infected wound healing - Junyao Song; Haoyu Chen; Yaqian Lv; Wanqun Yang; Fenglang Zhang; Tianyi Wang; Danping Liu; Yingshan Qu; Lei Han; Jun Fu; Xiaoying Kong (Chemical Engineering Journal, 2023)

Highly efficient endosperm and pericarp protoplast preparation system for transient transformation of endosperm-related genes in wheat - Shichen Han; Ge Qu; Xiaohui Li; Feixiong Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Reproducible Abnormalities and Diagnostic Generalizability of White Matter in Alzheimer’s Disease - Yida Qu; Pan Wang; Hongxiang Yao; Dawei Wang; Chengyuan Song; Hongwei Yang; Zengqiang Zhang; Pindong Chen; Xiaopeng Kang; Kai Du; Lingzhong Fan; Bo Zhou; et al. (Neuroscience Bulletin, 2023)

The activation of Wnt signaling facilitates autophagy by modulating GSK-3β-AMPK axis in atherosclerosis - Shifang Qu; Kuanxin Zhang; Nan Jin; Han Li; Bin Nie (Molecular & Cellular Toxicology, 2023)

Arsenic pollution, geochemical fractions, and leaching characteristics in soil samples from four contaminated sites in the Beijiang River Basin, South China - Yu-Zhong Liu; Jun-Feng Wang; Han-Yun Fan; Tao He; Dao-Yuan Wang; Huan-Zhan Zhou; Qu-Sheng Li (Environmental Science and Pollution Research, 2023)

Self-assembled nanoparticle with E protein domain III of DTMUV based on ferritin as carrier can induce a more comprehensive immune response and against DTMUV challenge in duck - Zhehui Qu; Xian Wu; Xiaoqiu Guo; Han Han; Peipei Zhang; Mengxiao Wang; Yilin Song; Fengchao Jiao; Shuhai He; Shaofang Lu; Xiwen Zhang (Veterinary Microbiology, 2023)

S-doped core–shell heterojunction Fenton catalyst (Fe3O4-S@PVP@UIO-66-(SH)2) for enhanced activation of hydroxyl radicals: Synergistic enrichment and degradation mechanism - Dingtang Li; Wei Qu; Bo Han; Jun Gao; Shuyu Xie; Dongmei Chen (Chemical Engineering Journal, 2023)

Nano-elemental selenium particle developed via supramolecular self-assembly of chondroitin sulfate A and Na2SeO3 to repair cartilage lesions - Jing Han; Huan Deng; Yang Li; Lichun Qiao; Hongrui Jia; Lan Zhang; Linghang Wang; Chengjuan Qu (Carbohydrate Polymers, 2023)

Effects of Intercropping Oat and Common Vetch on Plant Biomass Yield and Soil Nitrogen and Phosphorus Availability in Different Soil Characteristics - Jiahui Qu; Lijun Li; Peiyi Zhao; Tingting Zhang; Guangmin Chen; Jinhu Yang; Dongyu Han (Journal of Soil Science and Plant Nutrition, 2023)

Precipitation weakens the gravesoil fungal richness and species interactions in the Qinghai-Tibet Plateau - Binghua Han; Qiaoling Yu; Qian Han; Sijie Wang; Wanghong Su; Jiapeng Qu; Huan Li (Applied Soil Ecology, 2023)

Applicability of core-shell SiO2 microspheres with a high TiO2 loading as stationary phase for HPLC - Dian Wang; Xiang Wan; Jiafei Wang; Debby Mangelings; Qin Xu; Fazhi Xie; Xianhuai Huang; Weihua Li; Han Xuan; Wensheng Zou; Qishu Qu (Analytica Chimica Acta, 2023)

Identifying changes in the hydrological connectivity and their drivers in the Liaohe Delta wetland - Kexin Chen; Pifu Cong; Limei Qu; Shuxiu Liang; Zhaochen Sun; Jianbo Han (Ocean & Coastal Management, 2023)

Organic fertilization integrated with water management to remediate As and Cd contamination in a paddy soil - Pan Sun; Chenchen Qu; Zhenqian Xiong; Yafeng Han; Fuhai Ma; Peng Cai; Wenli Chen; Qiaoyun Huang (Science of The Total Environment, 2023)

Combined effects of amoxicillin and copper on nitrogen transformation and the microbial mechanisms during aerobic composting of cow manure - Ya Su; Jinpeng Xiong; Chen Fang; Huiwen Qu; Lujia Han; Xueqin He; Guangqun Huang (Journal of Hazardous Materials, 2023)

Breaking the cost barrier: polydopamine@NixCo100-x nanotubes as efficient photocatalysts for organic pollutant degradation - Qianqian Zeng; Hongjun Lin; Yang Qu; Zhengyi Huang; Ning Kong; Lei Han; Cheng Chen; Bisheng Li; Jiaheng Teng; Yanchao Xu; Liguo Shen (Journal of Cleaner Production, 2023)

Controlled deposition via a bifunctional layer enables dendrite-free zinc metal batteries - Han Wang; Quanyu Li; Shaozhen Huang; Liangjun Zhou; Lin Mei; Zhibin Wu; Baihua Qu; Weifeng Wei; Xiaobo Ji; Yuejiao Chen; Libao Chen (Chemical Engineering Journal, 2023)

Identification of driving factors of lignocellulose degrading enzyme genes in different microbial communities during rice straw composting - Fengting Qu; Hanpeng Cheng; Ziyi Han; Zimin Wei; Caihong Song (Bioresource Technology, 2023)

Parerythrobacter lacustris sp. nov., a novel member of the family Erythrobacteraceae isolated from an inland alpine lake - Maripat Xamxidin; Han Dong; Jia-Yan Wang; Wu Qu; Lin Xu; Min Wu (Archives of Microbiology, 2023)

Remediation of water tainted with noxious aspirin and fluoride ion using UiO-66-NH2 loaded peanut shell - Xiaoting Zhang; Xiaoyu Han; Yang Liu; Runping Han; Rong Wang; Lingbo Qu (Environmental Science and Pollution Research, 2023)

Metagenomics reveals elevated temperature causes nitrogen accumulation mainly by inhibiting nitrate reduction process in polluted water - Jiawei Yang; Qiaoling Yu; Wanghong Su; Sijie Wang; Xiaochen Wang; Qian Han; Jiapeng Qu; Huan Li (Science of The Total Environment, 2023)

Valorisation of food waste for valuable by-products generation with economic assessment - Xietian Zheng; Xikai Chen; Anlan Qu; Wenjing Yang; Lu Tao; Feiyue Li; Jingang Huang; Xiaobin Xu; Junhong Tang; Pingzhi Hou; Wei Han (Journal of Environmental Management, 2023)

Analysis and simulation of nitrogen loss during water erosion process on windward slope under wind-driven rain conditions - Miaoying An; Weiming Xing; Yuguo Han; Jinxing Zhou; Zhixu Qu; Chenyang Zhao; Pan Xu (CATENA, 2023)

Dominant modes and mechanisms of atmospheric rivers in East Asia - Shulin Qu; Tao Su; Zixuan Han; Bicheng Huang; Guolin Feng (Atmospheric Research, 2023)

Baicalein sensitizes triple negative breast cancer MDA-MB-231 cells to doxorubicin via autophagy-mediated down-regulation of CDK1 - Fang Hua; Yi-Yi Xiao; Xin-Hui Qu; Shan-Shan Li; Kun Zhang; Chao Zhou; Jian-Le He; Ye Zhu; Yu-Ying Wan; Li-Ping Jiang; Fang-Fang Tou; Xiao-Jian Han (Molecular and Cellular Biochemistry, 2023)

Strontium isotope ratios in kidney stones reveal the environmental implications for humans in Beijing, China - Rui Qu; Guilin Han; Yu Tian; Ye Zhao (Environmental Geochemistry and Health, 2023)

Fe contents and isotopes in suspended particulate matter of Lancang River in Southwest China - Yang Tang; Guilin Han; Liu Man; Jie Zeng; Rui Qu (Science of The Total Environment, 2023)

Selenium in soil-plant system: Transport, detoxification and bioremediation - Lili Qu; Jiayang Xu; Zhihua Dai; Ali Mohamed Elyamine; Wuxing Huang; Dan Han; Bingjun Dang; Zicheng Xu; Wei Jia (Journal of Hazardous Materials, 2023)

Does the aging behavior of microplastics affect the process of denitrification by the difference of copper ion adsorption? - Lanxi Li; Mengli Chen; Shushan Liu; Huanyu Bao; Dongxu Yang; Han Qu; Yi Chen (Journal of Hazardous Materials, 2023)

Degradation mechanisms of 2-chlorophenol by Acinetobacter sp.: Exploring cellular membrane structure, intra- and extracellular components, and transcriptomic analysis - Han Lin; Wenqi Guan; Yibo Xiao; Yujiao Qu; Yuan Ren (Journal of Environmental Chemical Engineering, 2023)

Effects of buckwheat milk Co-fermented with two probiotics and two commercial yoghurt strains on gut microbiota and production of short-chain Fatty Acids - Yang Wang; Sijia Qu; Menghan Chen; Yue Cui; Chenshan Shi; Xiaolu Pu; Wenhui Gao; Quanhong Li; Junhua Han; Aixia Zhang (Food Bioscience, 2023)

Quantifying the Impact of Hydrological Connectivity on Salt Marsh Vegetation in the Liao River Delta Wetland - Kexin Chen; Limei Qu; Pifu Cong; Shuxiu Liang; Zhaochen Sun; Jianbo Han (Wetlands, 2023)

Bimetallic adsorbents for wastewater treatment: a review - Aaron Albert Aryee; Yang Liu; Runping Han; Lingbo Qu (Environmental Chemistry Letters, 2023)

Bacterial cellulose-based hydrogel with antibacterial activity and vascularization for wound healing - Lili Deng; Yinjun Huang; Shiyan Chen; Zhiliang Han; Zhengzhe Han; Mengtian Jin; Xiangyang Qu; Baoxiu Wang; Huaping Wang; Song Gu (Carbohydrate Polymers, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Influence of temperature on fouling removal for pipeline based on eco-friendly ultrasonic guided wave technology - Mingkun Huang; Cong Han; Yang An; Zhigang Qu; Chuanxian Chen; Wuliang Yin (Clean Technologies and Environmental Policy, 2023)

Adsorption of 2,4-dichlorophenoxyacetic acid and glyphosate from water by Fe3O4-UiO-66-NH2 obtained in a simple green way - Xiaoting Zhang; Yang Liu; Lingbo Qu; Runping Han (Environmental Science and Pollution Research, 2023)

A new insight into the low membrane fouling tendency of liquid-liquid hollow fiber membrane contactor capturing ammonia from human urine - Junhui Zhang; Kuiling Li; Mengfei Xie; Qi Han; Li Feng; Dan Qu; Liqiu Zhang; Ke Wang (Water Research, 2023)

Simulation and risk assessment of arsenic by Hydrus-3D and CalTOX in a typical brownfield site - Tianhao He; Ye Li; Ye Huang; Erkai He; Yan Li; Liangyu Qu; Fangfang Ding; Ruihe Jin; Mingzhe Han; Lina Yuan; Weizhen Xue; Ruijuan Qu; et al. (Journal of Hazardous Materials, 2023)

Effects of micro-positive pressure environment on nitrogen conservation and humification enhancement during functional membrane-covered aerobic composting - Jinpeng Xiong; Ya Su; Huiwen Qu; Lujia Han; Xueqin He; Jianbin Guo; Guangqun Huang (Science of The Total Environment, 2023)

Effect of oxygen functional groups on competitive adsorption of benzene and water on carbon materials: Density functional theory study - Haiqian Zhao; Ziyu Tang; Mingqi He; Xue Yang; Shiwei Lai; Kaibo An; Shuaishuai Han; Zhibin Qu; Wei Zhou; Zhonghua Wang (Science of The Total Environment, 2023)

Metagenomic study of carbon metabolism in black soil microbial communities under lead-lanthanum stress - Yue Tao; Lu Shen; Siyue Han; Zixu Li; Yunhe Cui; Yulong Lin; Jianhua Qu; Ying Zhang (Journal of Hazardous Materials, 2023)

Hydrology and water quality shape macroinvertebrate patterns and facilitate non-native species dispersals in an inter-basin water transfer system - Xiao Qu; Julian D. Olden; Wentong Xia; Han Liu; Zhicai Xie; Robert M. Hughes; Yushun Chen (Journal of Environmental Management, 2023)

Pyrometallurgy treatment of electroplating sludge, emulsion mud and coal ash: ZnAlFeO4 spinel separation and stabilization in calcium metasilicate glass - Qin Jiabao; Qu Zhan; Chen Hongyu; Wang Zhihua; Han Qi; Zhang Yuxin; Zhang Hong; Gao Yidi; Zhang Ying; Wang Xianze; Zhu Suiyi (Journal of Environmental Management, 2023)

An ultra-sensitive photothermal lateral flow immunoassay for 17β-estradiol in food samples - Yi Zhang; Han-Jie Yang; Zhenghua Xu; Xiao Liu; Jie Zhou; Xu-Fang Qu; Wen-Long Wang; Yongwei Feng; Chifang Peng (Food Chemistry, 2023)

A first wind tunnel study on the aeolian sand transport of coral sands - Benli Liu; Jianjun Qu; Lihai Tan; Zhishan An; Hongtao Wang; Tao Wang; Qingjie Han (CATENA, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Tetrapeptide-based mimotope affinity monolith for the enrichment and analysis of anti-HER2 antibody and antibody-drug conjugate - Chendi Zhu; Hai Han; Zhiwei Chen; Yuan Shen; Qiaoxuan Zhang; Cai Bao; Jia-Huan Qu; Qiqin Wang; Zhengjin Jiang (Analytica Chimica Acta, 2023)

Seasonal variation of transit time distribution and associated hydrological processes in a Moso bamboo watershed under the East Asian monsoon climate - Jianfeng Gou; Simin Qu; Huade Guan; Peng Shi; Zhicai Zhang; Hai Yang; Jintao Liu; Zhiguo Su; Xiaole Han (Journal of Hydrology, 2023)

Assessment of β-cyclodextrin-immobilizing hydrolyzed polyacrylonitrile membrane for enhanced remediation of bisphenol A and tetracyclines: Adsorption and antibacterial studies - Mingyu Liu; Chenping Gao; Runping Han; Lingbo Qu (Journal of Cleaner Production, 2023)

Hydrometallurgy recovery of copper, aluminum and silver from spent solar panels - Qi Han; Yidi Gao; Ting Su; Jiabao Qin; Chi Wang; Zhan Qu; Xianze Wang (Journal of Environmental Chemical Engineering, 2023)

Novel supported low-temperature solid molten salt (SMS) anode materials for Li-ion batteries - Lei Jiang; Ning Han; Tingting Luo; Zhe Zhang; Fenghao Liang; Daoning Wu; Xiaochun Li; Fengjiao Liu; Yichuan Rui; Wei Zhang; Yi Qu; Bohejin Tang (Chemical Engineering Journal, 2023)

Asymmetric intramolecular charge transfer enables highly efficient red thermally activated delayed fluorescent emitters - Chao Qu; Huiqin Wang; Yi Man; Zhe Li; Peng Ma; Peng Chang; Xin Li; Chunmiao Han; Yudong Pang; Hui Xu (Chemical Engineering Journal, 2023)

Sandwich-structured nickel/kaolinite catalyst with boosted stability for dry reforming of methane with carbon dioxide - Hao Qu; Hui Yang; Libo Han; Sihui He; Jiadong Liu; Ruijue Hu; Haiquan Su; Yue Su (Chemical Engineering Journal, 2023)

Mechanisms of the formation of wind-blown sand hazards and the sand control measures in Gobi areas under extremely strong winds along the Lanzhou-Xinjiang high-speed railway - Jianjun Qu; Tao Wang; Qinghe Niu; Benli Liu; Lihai Tan; Qingjie Han; Yang Gao; Jianhua Xiao (Science China Earth Sciences, 2023)

Potassium isotopes of fertilizers as potential markers of anthropogenic input in ecosystems - Rui Qu; Guilin Han (Environmental Chemistry Letters, 2023)

Remediation of water tainted with noxious hexavalent chromium using cetylpyridinium-modified bagasse biomass: adsorption and regeneration studies - Farid Mzee Mpatani; Aaron Albert Aryee; Lingbo Qu; Runping Han (Environmental Science and Pollution Research, 2023)

Di-(2-ethylhexyl) phthalate aggravates fine particulate matter-induced asthma in weanling mice due to T follicular helper cell-dependent response - Yu Han; Xiangjun Yu; Ying Lu; Yi Shen; Xiaoying Wang; Haiyan Wei; Kaihua Ni; Jianhua Qu; Gang Chen (Toxicology, 2023)

Response of dissolved organic carbon in rainwater during extreme rainfall period in megacity: Status, potential source, and deposition flux - Jie Zeng; Guilin Han; Shitong Zhang; Xuhuan Xiao; Yikai Li; Xi Gao; Di Wang; Rui Qu (Sustainable Cities and Society, 2023)

Nitrate dynamics and source identification of rainwater in Beijing during rainy season: Insight from dual isotopes and Bayesian model - Jie Zeng; Guilin Han; Shitong Zhang; Rui Qu (Science of The Total Environment, 2023)

Associations of personal exposure to domestic heating and cooking fuel emissions and epidemiological effects on rural residents in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Yue Cheng; Bei Han; Kin Fai Ho; Zexuan Wang; Yansu He; Linli Qu; Steven Sai Hang Ho; Jian Sun; Zhenxing Shen; et al. (Science of The Total Environment, 2023)

A 3D smart wood membrane with high flux and efficiency for separation of stabilized oil/water emulsions - Jianfei Wu; Ziwei Cui; Yang Yu; He Han; Dan Tian; Jundie Hu; Jiafu Qu; Yahui Cai; Jianlin Luo; Jianzhang Li (Journal of Hazardous Materials, 2023)

Resource utilization of bovine bone to prepare biochar as persulfate activator for phenol degradation - Mingze Sun; Jianhua Qu; Tianyi Han; Jiaqi Xue; Kaige Li; Zhao Jiang; Guangshan Zhang; Hui Yu; Ying Zhang (Journal of Cleaner Production, 2023)

Superwettable Surface-Dependent efficiently electrocatalytic water splitting based on their excellent liquid adsorption and gas desorption - Fei Zhang; Ran Zhao; Yiran Wang; Lu Han; Jianmin Gu; Zhimin Niu; Yiming Yuan; Nianrui Qu; Jingxin Meng; Desong Wang (Chemical Engineering Journal, 2023)

Inspired by philosophizing of “point to area”: Ion pre-intercalation induces the reconstitution of interlayer environment of MXene for lithium storage - Miao Liu; Xin Qu; Yixuan Wang; Yukai Zhang; Cuimei Zhao; Bo Liu; Xiangxin Xue; Junkai Zhang; Zhao Wang; Jiaming Li; Wenjuan Han; Shichong Xu; et al. (Chemical Engineering Journal, 2023)

Arsenic trioxide promotes ERK1/2-mediated phosphorylation and degradation of BIMEL to attenuate apoptosis in BEAS-2B cells - Yilun Liang; Yun Qian; Jing Tang; Chenjuan Yao; Shali Yu; Jianhua Qu; Haiyan Wei; Gang Chen; Yu Han (Chemico-Biological Interactions, 2023)

Local and Global Abnormalities in Pre-symptomatic Huntington’s Disease Revealed by 7T Resting-state Functional MRI - Juan-Juan Xie; Xiao-Yan Li; Yi Dong; Cong Chen; Bo-Yi Qu; Shuang Wang; Han Xu; Anna Wang Roe; Hsin-Yi Lai; Zhi-Ying Wu (Neuroscience Bulletin, 2023)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Biocomposite based on zirconium and amine-grafted walnut shell with antibacterial properties for the removal of Alizarin red in water: batch and column studies - Evans Dovi; Aaron Albert Aryee; Mingyu Liu; Xiaoting Zhang; Alexander Nti Kani; Jianjun Li; Runping Han; Lingbo Qu (Environmental Science and Pollution Research, 2022)

Steeply dipping structural target-oriented viscoacoustic least-squares reverse time migration and its application - Kang Chen; Song Han; Qi Ran; Long Wen; Guang-Zhi Zhang; Ying-Ming Qu (Applied Geophysics, 2022)

Exploring associations between urine levels of phthalates and autism spectrum disorder symptoms: a case–control study in Tianjin, China - Yu Han; Shihao Jin; Liyuan Liu; Zhiyi Qu; Lei Gao; Peiying Li; Wenjuan Xiong; Xin Zhang (Environmental Science and Pollution Research, 2022)

Acid-washed zero-valent aluminum as a highly efficient persulfate activator for degradation of phenacetin - Junxue Wu; Bin Wang; Han Qu; Fang Wang; Lei Duan; Gang Yu (Environmental Science and Pollution Research, 2022)

Progress of Selenium Deficiency in the Pathogenesis of Arthropathies and Selenium Supplement for Their Treatment - Huan Deng; Haobiao Liu; Zhihao Yang; Miaoye Bao; Xue Lin; Jing Han; Chengjuan Qu (Biological Trace Element Research, 2022)

A Highly Selective Fluorescent Probe for the Detection of Nitroreductase Based on a Naphthalimide Scaffold - Han Li; Feng Jintao; Zhen Wang; Yan Jia; Peng Li; Cuixia Yao; Zongjin Qu (Journal of Fluorescence, 2022)

Efficient removal of 2,4-D from solution using a novel antibacterial adsorbent based on tiger nut residues: adsorption and antibacterial study - Alexander Nti Kani; Evans Dovi; Aaron Albert Aryee; Runping Han; Lingbo Qu (Environmental Science and Pollution Research, 2022)

Mechanisms responsible for interdecadal variation of the thermodynamic component of East Asian summer monsoon moisture transport - Tao Su; Yue Li; Bicheng Huang; Shulin Qu; Zixuan Han; Zhonghua Qian; Guolin Feng; Yongping Wu (International Journal of Climatology, 2022)
In this study, the East Asian summer (June–July–August) monsoon (EASM) atmospheric moisture transport variability under global warming are examined using ERA‐Interim reanalysis data from 1979 to 2019. The total EASM atmospheric moisture transport is decomposed into the thermodynamic (δTH) and dynamic (δMCD) components, which are related to specific humidity and wind velocity, respectively. Based on empirical orthogonal function (EOF) analysis, both the second and the fourth modes of δTH are linked to δMCD, indicating that δMCD can impact the moisture distribution and consequently influence δTH indirectly. Both the first (δTH_EOF1) and the third (δTH_EOF3) modes of δTH show considerable interdecadal changes. It is noted that their principal components exhibit significant increasing trends in recent decades. The response of EASM moisture transport to global warming is probably reflected in these two modes. δTH_EOF1 is associated with negative phases of the Interdecadal Pacific Oscillation (IPO)/Pacific Decadal Oscillation (PDO). This causes the western North Pacific subtropical high (WNPSH) to extend westward and the strengthening of Pacific trade winds. As a result, positive precipitable water anomalies dominate East Asia and δTH_EOF1 is characterized by anomalous southwesterly moisture transport along the East China Sea to southern Japan. δTH_EOF3 corresponds to anomalous moisture transport over the Indochina Peninsula and Japan. The precipitable water associated with δTH_EOF3 in general represents a meridional dipole. Anomalous southward wind induced by the eastward extension of the WNPSH is the main reason for positive (negative) precipitable water anomalies in southern (northern) East Asian. The anomalous circulation associated with the anomalous east–west sea surface temperature gradient over the Indian Ocean affects atmospheric moisture in southern East Asian and can dramatically impact δTH_EOF3.

Metagenomics study to compare the taxonomic composition and metabolism of a lignocellulolytic microbial consortium cultured in different carbon conditions - Qinggeer Borjigin; Bizhou Zhang; Xiaofang Yu; Julin Gao; Xin Zhang; Jiawei Qu; Daling Ma; Shuping Hu; Shengcai Han (World Journal of Microbiology and Biotechnology, 2022)

Activation of the GPX4/TLR4 Signaling Pathway Participates in the Alleviation of Selenium Yeast on Deltamethrin-Provoked Cerebrum Injury in Quails - Jiayi Li; Zhongxian Yu; Bing Han; Siyu Li; Yueying Lv; Xiaoqiao Wang; Qingyue Yang; Pengfei Wu; Yuge Liao; Bing Qu; Zhigang Zhang (Molecular Neurobiology, 2022)

Microfossil analysis of dental calculus and isotopic measurements reveal the complexity of human-plant dietary relationships in Late Bronze Age Yunnan - Tingting Wang; Dong Wei; Zhilong Jiang; Xiumin Xia; Yan Wu; Zhen Han; Yating Qu; Yaowu Hu; Benjamin T. Fuller (Archaeological and Anthropological Sciences, 2022)

Comparison of separated and combined photodegradation and biofiltration technology for the treatment of volatile organic compounds: A critical review - Meng-Fei Han; Xu-Rui Hu; Yong-Chao Wang; Zhen Tong; Can Wang; Zhuo-Wei Cheng; Ke Feng; Miao-Miao Qu; Jian-Meng Chen; Ji-Guang Deng; Hsing-Cheng Hsi (Critical Reviews in Environmental Science and Technology, 2022)

Amine-grafted walnut shell for efficient removal of phosphate and nitrate - Evans Dovi; Aaron Albert Aryee; Jianjun Li; Zhaohui Li; Lingbo Qu; Runping Han (Environmental Science and Pollution Research, 2022)

Testing the impact of first-mover advantage on household energy-related carbon emissions: an exploratory study from six urban agglomerations in China - Jingjing Zeng; Li Xu; Jiansheng Qu; Jinyu Han; Jinjia Wu; Jing Bai; Hengji Li (Environmental Science and Pollution Research, 2022)

Pollutant decontamination by polyethyleneimine-engineered agricultural waste materials: a review - Alexander Nti Kani; Evans Dovi; Farid Mzee Mpatani; Aaron Albert Aryee; Runping Han; Zhaohui Li; Lingbo Qu (Environmental Chemistry Letters, 2022)

Comprehensive analysis of chloroplast genome of Albizia julibrissin Durazz. (Leguminosae sp.) - Jing Zhang; Huizhen Huang; Changqing Qu; Xiaoxi Meng; Fei Meng; Xiaoyan Yao; Jing Wu; Xiaohu Guo; Bangxing Han; Shihai Xing (Planta, 2022)

CRISPR-Cas systems are present predominantly on chromosome and its relationship with MEGs in Vibrio species - Enbao Zhang; Wei Zhou; Jinzhi Zhou; Ze He; Yuqiao Zhou; Jianzhong Han; Daofeng Qu (Archives of Microbiology, 2022)

Karyotypic stability of Fragaria (strawberry) species revealed by cross-species chromosome painting - Manman Qu; Luyue Zhang; Kunpeng Li; Jianying Sun; Zongyun Li; Yonghua Han (Chromosome Research, 2021)

Fitness cost and compensation mechanism of sulfonamide resistance genes ( sul1 , sul2 , and sul3 ) in Escherichia coli - Yuqiao Zhou; Jiehong Fang; Zaeim Davood; Jianzhong Han; Daofeng Qu (Environmental Microbiology, 2021)
Summary The fitness cost of antibiotic resistance is a crucial factor to determine the evolutionary and transmission success of resistant bacteria. Exploring the fitness cost and compensation mechanism of antibiotic resistance genes (ARGs) in bacteria may effectively reduce the transmission of drug‐resistant genes in the environment. Engineered bacteria with the same genetic background that carry sulfonamide resistance gene were generated to explore the fitness cost of sulfonamide resistance gene in Escherichia coli . There were significant differences in the protein expression of the two‐component system pathway ( fliZ , fliA , fliC and lrhA ), folate biosynthesis pathway ( sul1 , sul2 and sul3 ), ABC transporter system ( ugpC , rbsA and gsiA ), and outer membrane pore protein OmpD through the comparative analysis of differential proteins compared to sensitive bacteria. Thus, we could speculate the possible fitness compensation mechanism. Finally, quantitative Real‐time PCR (qRT‐PCR) was used to verify the functions of some differential proteins at the transcriptional level. The fitness cost and compensatory evolution of antibiotic resistance are an essential part of bacterial evolution.

Magnetic monitoring of topsoil and street dust in Xinyang (China) and their environmental implications - Yan Han; Xiuming Liu; Guoyong Zhao; Bin Lü; Qu Chen (Environmental Monitoring and Assessment, 2021)

Short-term effects of soil moisture on soil organic carbon decomposition in a coastal wetland of the Yellow River Delta - Wendi Qu; Guangxuan Han; Jian Wang; Juanyong Li; Mingliang Zhao; Wenjun He; Xinge Li; Siyu Wei (Hydrobiologia, 2021)

Multi-model fusion based on MATLAB to identify the water quality between the wet season and the drought period in Changyi water source area - Xingyue Qu; Jin Han; Mei Qiu; Weifu Gao (Arabian Journal of Geosciences, 2021)

Selective removal of anionic dyes in single and binary system using Zirconium and iminodiacetic acid modified magnetic peanut husk - Aaron Albert Aryee; Evans Dovi; Qiehui Guo; Mingyu Liu; Runping Han; Zhaohui Li; Lingbo Qu (Environmental Science and Pollution Research, 2021)

Decontamination of bisphenol A and Congo red dye from solution by using CTAB functionalised walnut shell - Evans Dovi; Alexander Nti Kani; Aaron Albert Aryee; Ma Jie; Jianjun Li; Zhaohui Li; Lingbo Qu; Runping Han (Environmental Science and Pollution Research, 2021)

Unraveling Physiological and Metabolomic Responses Involved in Phlox subulata L. Tolerance to Drought Stress - Yan Xiong; Yanting Qu; Hui Han; Fei Chen; Li Li; Huanwei Tang; Daidi Che; Xing Zhang (Plant Molecular Biology Reporter, 2021)

Gga-miR-181a modulates ANP32A expression and inhibits MDCC-MSB-1 cell - X. Li; C. Zhao; B. Han; L. Qu; C. Liu; N. Yang; L. Lian (In Vitro Cellular & Developmental Biology - Animal, 2021)

Construction of a new plant expression vector and the development of maize germplasm expressing the Aspergillus ficuum phytase gene PhyA2 - Peng Jiao; Wen-Ya Yuan; Han-Dan Zhao; Jing Qu; Pi-Wu Wang; Shu-Yan Guan; Yi-Yong Ma (Genetic Resources and Crop Evolution, 2021)
Phytases, which belong to a special category of orthophosphoric monoester phosphohydrolases, degrade inositol hexaphosphate to produce lower-grade inositol phosphate derivatives and inorganic phosphate. Thus, phytases may improve phosphorus utilization, eliminate the anti-nutrient properties of phytic acid, and mitigate environmental pollution due to phosphorus contamination. In this study, we constructed a new root-specific expression vector by inserting the Aspergillus ficuum phytase gene PhyA2 into pCAMBIA3301-ZmGLU1P-Nos. The subsequent molecular analysis confirmed that six T 4 generation transgenic plants carried and expressed PhyA2 . A quantitative real-time PCR analysis indicated PhyA2 was highly expressed in the transgenic roots. Additionally, the phytase activity was 10.9-fold higher in the transgenic roots (peak activity of 5.432 U/g) than in the control roots. Moreover, compared with the control rhizosphere, the organic phosphorus content in the rhizosphere of the transgenic plants decreased significantly (by up to 5.21 mg/kg). An agronomic trait analysis indicated that PhyA2 expression can increase maize seed weight by up to 25.8 g. Therefore, the integration of PhyA2 into the maize genome can enhance the ability of maize plants to use the phosphorus compounds in soil, while also improving the plant growth status and increasing the seed yield.

The development and application of China national landslide database and information system - Bin Tong; Yuan Li; Xudong Yang; Chunrong Yin; Xueyan Qu; Hao Fang; Bing Han; Yanling Zhang (Arabian Journal of Geosciences, 2021)

Determination of Landscape Ecological Network of Wetlands in the Yellow River Delta - Pifu Cong; Kexin Chen; Limei Qu; Jianbo Han; Zhengxian Yang (Wetlands, 2020)

The Landscape of Micro-Inversions Provide Clues for Population Genetic Analysis of Humans - Li Qu; Luotong Wang; Feifei He; Yilun Han; Longshu Yang; May D. Wang; Huaiqiu Zhu (Interdisciplinary Sciences: Computational Life Sciences, 2020)
Background Variations in the human genome have been studied extensively. However, little is known about the role of micro-inversions (MIs), generally defined as small (< 100 bp) inversions, in human evolution, diversity, and health. Depicting the pattern of MIs among diverse populations is critical for interpreting human evolutionary history and obtaining insight into genetic diseases. Results In this paper, we explored the distribution of MIs in genomes from 26 human populations and 7 nonhuman primate genomes and analyzed the phylogenetic structure of the 26 human populations based on the MIs. We further investigated the functions of the MIs located within genes associated with human health. With hg19 as the reference genome, we detected 6968 MIs among the 1937 human samples and 24,476 MIs among the 7 nonhuman primate genomes. The analyses of MIs in human genomes showed that the MIs were rarely located in exonic regions. Nonhuman primates and human populations shared only 82 inverted alleles, and Africans had the most inverted alleles in common with nonhuman primates, which was consistent with the “Out of Africa” hypothesis. The clustering of MIs among the human populations also coincided with human migration history and ancestral lineages. Conclusions We propose that MIs are potential evolutionary markers for investigating population dynamics. Our results revealed the diversity of MIs in human populations and showed that they are essential to construct human population relationships and have a potential effect on human health.

Enhanced adsorption of copper ions by phosphoric acid-modified Paeonia ostii seed coats - Qiong Liu; Runping Han; Lingbo Qu; Baozeng Ren (Environmental Science and Pollution Research, 2020)

Petrogenesis of post-collisional magmatism at the Carboniferous–Permian boundary in central Inner Mongolia, NE China: insights into when the Hegenshan Ocean closed? - Lu Lu; Yong Qin; Kai-Jun Zhang; Chun-Yuan Han; Zhuang-Fu Li; Tao Wei; Zheng-Hui Qu; Yong-Zhong Xu (International Geology Review, 2020)

Iminodiacetic acid functionalized magnetic peanut husk for the removal of methylene blue from solution: characterization and equilibrium studies - Aaron Albert Aryee; Farid Mzee Mpatani; Alexander Nti Kani; Evans Dovi; Runping Han; Zhaohui Li; Lingbo Qu (Environmental Science and Pollution Research, 2020)

Effects of Drying-Rewetting Frequency on Vertical and Lateral Loss of Soil Organic Carbon in a Tidal Salt Marsh - Juanyong Li; Wendi Qu; Guangxuan Han; Feng Lu; Yingfeng Zhou; Weimin Song; Baohua Xie; Franziska Eller (Wetlands, 2020)

Inundation depth affects ecosystem CO2 and CH4 exchange by changing plant productivity in a freshwater wetland in the Yellow River Estuary - Mingliang Zhao; Guangxuan Han; Haitao Wu; Weimin Song; Xiaojing Chu; Juanyong Li; Wendi Qu; Xinge Li; Siyu Wei; Franziska Eller; Changsheng Jiang (Plant and Soil, 2020)

A sensitive and rapid bacterial antibiotic susceptibility test method by surface enhanced Raman spectroscopy - Shijie Fu; Xiwen Wang; Ting Wang; Zhiping Li; Deming Han; Chunsheng Yu; Cui Yang; Han Qu; Hang Chi; Yutian Wang; Song Li; Baihui Tian; et al. (Brazilian Journal of Microbiology, 2020)

Whole-Brain Monosynaptic Inputs to Hypoglossal Motor Neurons in Mice - Han Guo; Xiang-Shan Yuan; Ji-Chuan Zhou; Hui Chen; Shan-Qun Li; Wei-Min Qu; Zhi-Li Huang (Neuroscience Bulletin, 2020)
Hypoglossal motor neurons (HMNs) innervate tongue muscles and play key roles in a variety of physiological functions, including swallowing, mastication, suckling, vocalization, and respiration. Dysfunction of HMNs is associated with several diseases, such as obstructive sleep apnea (OSA) and sudden infant death syndrome. OSA is a serious breathing disorder associated with the activity of HMNs during different sleep–wake states. Identifying the neural mechanisms by which the state-dependent activities of HMNs are controlled may be helpful in providing a theoretical basis for effective therapy for OSA. However, the presynaptic partners governing the activity of HMNs remain to be elucidated. In the present study, we used a cell-type-specific retrograde tracing system based on a modified rabies virus along with a Cre/loxP gene-expression strategy to map the whole-brain monosynaptic inputs to HMNs in mice. We identified 53 nuclei targeting HMNs from six brain regions: the amygdala, hypothalamus, midbrain, pons, medulla, and cerebellum. We discovered that GABAergic neurons in the central amygdaloid nucleus, as well as calretinin neurons in the parasubthalamic nucleus, sent monosynaptic projections to HMNs. In addition, HMNs received direct inputs from several regions associated with respiration, such as the pre-Botzinger complex, parabrachial nucleus, nucleus of the solitary tract, and hypothalamus. Some regions engaged in sleep–wake regulation (the parafacial zone, parabrachial nucleus, ventral medulla, sublaterodorsal tegmental nucleus, dorsal raphe nucleus, periaqueductal gray, and hypothalamus) also provided primary inputs to HMNs. These results contribute to further elucidating the neural circuits underlying disorders caused by the dysfunction of HMNs.

Phenotypic assessment and ligand screening of ETA/ETB receptors with label-free dynamic mass redistribution assay - Lala Qu; Xiuli Zhang; Jixia Wang; Han Zhou; Tao Hou; Lai Wei; Fangfang Xu; Xinmiao Liang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Using water-level fluctuations in response to Earth-tide and barometric-pressure changes to measure the in-situ hydrogeological properties of an overburden aquifer in a coalfield - Qu Shen; Shi Zheming; Wang Guangcai; Xu Qingyu; Zhu Zejun; Han Jiaqian (Hydrogeology Journal, 2020)

Evaluation of the relationship between DNA methylation status and heterosis in soybean with MethylRAD technique - Baixing Song; Yuanqian Wang; Songnan Yang; Xueying Li; Xiao Han; Sujie Fan; Abraham Lamboro; Dan Yao; Jing Qu; Zhuo Zhang; Yang Song; Jun Zhang (Euphytica, 2020)

Impact of the Three Gorges Dam on the Quality of Riverine Dissolved Organic Matter - Fanchao Xu; Liming Chen; Yifan Xu; Han Gao; He Cui; Peiyun Wei; Xiaolei Qu (Bulletin of Environmental Contamination and Toxicology, 2020)

Diversity Distributions and the Anthocyanin Associations of Fungal Endophytes in Different Colored Grapevine Leaves - Jing-Chao Chen; Man Yu; Fang Liu; Jin-Zhuo Qu; Xiao-Xia Pan; Han-Bo Zhang; Ming-Zhi Yang (Journal of Plant Biology, 2020)

Abnormal expression of chondroitin sulfate sulfotransferases in the articular cartilage of pediatric patients with Kashin–Beck disease - Jian Lei; Siqi Yan; Yuan Zhou; Liyun Wang; Jinghua Zhang; Xiong Guo; Mikko J. Lammi; Jing Han; Chengjuan Qu (Histochemistry and Cell Biology, 2020)

Serious Selenium Deficiency in the Serum of Patients with Kashin–Beck Disease and the Effect of Nano-Selenium on Their Chondrocytes - Liyun Wang; Jiafeng Yin; Bo Yang; Chengjuan Qu; Jian Lei; Jing Han; Xiong Guo (Biological Trace Element Research, 2020)

Rolling–sliding load decreases the loss of chondrocyte viability and the mechanical properties of cartilage explants preserved in vitro - Jianhong Qi; Chao Jin; Pengwei Qu; Lu Zhou; Di Xie; Hongqiang Song; Meng Men; Yunning Han; Caiyun Geng; Famin Cao; Yadi Wu (Cell and Tissue Banking, 2019)

Spatial Distribution and Congener Profiles of Polybrominated Diphenyl Ethers in Surface Sediment from Sanmen Bay and Xiamen Bay, Southeast China - Kunyan Liu; Yong Qiu; Shanshan Zhou; Kunde Lin; Da Chen; Han Qu; Xiaodong Wang; Yongxia Hu; Yan Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Decreased Expression of CHST-12, CHST-13, and UST in the Proximal Interphalangeal Joint Cartilage of School-Age Children with Kashin–Beck Disease: an Endemic Osteoarthritis in China Caused by Selenium Deficiency - Yijie Guo; Yuan Zhou; Siqi Yan; Chengjuan Qu; Liyun Wang; Xiong Guo; Jing Han (Biological Trace Element Research, 2019)

Toll-Like Receptor 4 Promotes Th17 Lymphocyte Infiltration Via CCL25/CCR9 in Pathogenesis of Experimental Autoimmune Encephalomyelitis - Ying Zhang; Jingjing Han; Meili Wu; Lu Xu; Yu Wang; Wen Yuan; Fang Hua; Hongbin Fan; Fuxing Dong; Xuebin Qu; Ruiqin Yao (Journal of Neuroimmune Pharmacology, 2019)

Polyhalogenated Carbazoles in Surface Sediment from Sanmen Bay, East China Sea: Spatial Distribution and Congener Profile - Yong Qiu; Kunyan Liu; Shanshan Zhou; Da Chen; Han Qu; Xiaodong Wang; Yongxia Hu; Yan Wang (Bulletin of Environmental Contamination and Toxicology, 2019)

Genome-wide association study of inflorescence length of cultivated soybean based on the high-throughout single-nucleotide markers - Jinyang Wang; Xue Zhao; Wei Wang; Yingfan Qu; Weili Teng; Lijuan Qiu; Hongkun Zheng; Yingpeng Han; Wenbin Li (Molecular Genetics and Genomics, 2019)

Dynamic Changes in the Wetland Landscape Pattern of the Yellow River Delta from 1976 to 2016 Based on Satellite Data - Pifu Cong; Kexin Chen; Limei Qu; Jianbo Han (Chinese Geographical Science, 2019)

Storage solution containing hydrogen improves the preservation effect of osteochondral allograft - Yunning Han; Pengwei Qu; Kaihong Zhang; Yikang Bi; Lu Zhou; Di Xie; Hongqiang Song; Jun Dong; Jianhong Qi (Cell and Tissue Banking, 2019)

Pseudofrancisella aestuarii gen. nov., sp. nov., a novel member of the family Francisellaceae isolated from estuarine seawater - Min-Ling Zheng; Jian-Yu Jiao; Lei Dong; Ming-Xian Han; Liang-Hui Li; Min Xiao; Cha Chen; Ping-Hua Qu; Wen-Jun Li (Antonie van Leeuwenhoek, 2019)

Inhibition of thymocyte autophagy-associated CD4+T thymopoiesis is involved in asthma susceptibility in mice exposed to caffeine prenatally - Han-xiao Liu; Hui-yi Yan; Wen Qu; Xiao Wen; Li-fang Hou; Wen-hao Zhao; Jie Ping (Archives of Toxicology, 2019)

Prediction on landslide displacement using a new combination model: a case study of Qinglong landslide in China - Weidong Wang; Jiaying Li; Xia Qu; Zheng Han; Pan Liu (Natural Hazards, 2019)

Changes in global monsoon precipitation and the related dynamic and thermodynamic mechanisms in recent decades - Zixuan Han; Tao Su; Bicheng Huang; Taichen Feng; Shulin Qu; Guolin Feng (International Journal of Climatology, 2019)
The aim of this study is to explore the long‐term trends in the distribution of global monsoon precipitation over recent decades using the Global Precipitation Climatology Project (GPCP) data set. In addition, the potential4 mechanisms are examined by applying the atmospheric moisture budget decomposition method to the outputs from the ERA‐Interim medium‐range weather forecasting reanalysis produced by the European Centre for Medium‐Range Weather Forecasts (ECMWF). Changes in global monsoon precipitation are primarily thermodynamically caused by changes in specific humidity and dynamically caused by changes in circulation, as well as by changes in moisture transport that are driven by transient eddies and local evaporation. The results show that the increasing trends in global summer monsoon precipitation from 1979 to 2016 were dominated by contributions from the southern Asian, South African, and North American monsoon regions and were driven by the response of atmospheric circulation to the enhanced east–west thermal contrast in the tropical Pacific. We find that changes in the sea surface temperature (SST) patterns promote increased low‐level vertical velocities in monsoon regions, leading to moisture convergence through divergent circulation anomalies when combined with the climatological humidity field. Hence, the processes result in increasing trends in monsoon precipitation. In addition, evaporation makes increasing contributions to monsoon precipitation throughout the world, except in the South American monsoon region. Moreover, subtropical regions in the East Pacific (the Atlantic) may be major sources of water vapour that have supported increases in precipitation over the southern Asian and North American monsoon regions (the South African monsoon region) in recent decades.

Transcriptome sequencing to reveal the genetic regulation of leaf margin variation at early stage in birch - Xiuyan Bian; Chang Qu; Manman Zhang; Yidi Li; Rui Han; Jing Jiang; Guifeng Liu (Tree Genetics & Genomes, 2019)

Loci and candidate genes in soybean that confer resistance to Fusarium graminearum - Chanjuan Zhang; Xue Zhao; Yingfan Qu; Weili Teng; Lijuan Qiu; Hongkun Zheng; Zhenhua Wang; Yingpeng Han; Wenbin Li (Theoretical and Applied Genetics, 2019)

Effect of salinity on the decomposition of soil organic carbon in a tidal wetland - Wendi Qu; Juanyong Li; Guangxuan Han; Haitao Wu; Weimin Song; Xiaoshuai Zhang (Journal of Soils and Sediments, 2019)

Discovery of novel antagonists on β2-adrenoceptor from natural products using a label-free cell phenotypic assay - Pengyu Zhang; Jixia Wang; Ying Zhao; Xiuli Zhang; Lala Qu; Chaoran Wang; Jiatao Feng; Anhui Wang; Weijia Zhou; Yanfang Liu; Tao Hou; Han Zhou; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Low root/shoot (R/S) biomass ratio can be an indicator of low cadmium accumulation in the shoot of Chinese flowering cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee) cultivars - Zhi-Min Xu; Xiu-Qin Mei; Ling Tan; Qu-Sheng Li; Li-Li Wang; Bao-Yan He; Shi-Hong Guo; Chu Zhou; Han-Jie Ye (Environmental Science and Pollution Research, 2018)

Knockout of ush2a gene in zebrafish causes hearing impairment and late onset rod-cone dystrophy - Shanshan Han; Xiliang Liu; Shanglun Xie; Meng Gao; Fei Liu; Shanshan Yu; Peng Sun; Changquan Wang; Stephen Archacki; Zhaojing Lu; Xuebin Hu; Yayun Qin; et al. (Human Genetics, 2018)

Low-Cd tomato cultivars (Solanum lycopersicum L.) screened in non-saline soils also accumulated low Cd, Zn, and Cu in heavy metal-polluted saline soils - Zhi-Min Xu; Xiao-Qi Tan; Xiu-Qin Mei; Qu-Sheng Li; Chu Zhou; Li-Li Wang; Han-Jie Ye; Ping Yang (Environmental Science and Pollution Research, 2018)

De novo transcriptome analysis of an albino mutant Pasphiopedilum pacific shamrock reveals reduced expression of genes related to chloroplast biosynthesis and division - Han Li; Hua Cao; Rong-pei Yu; Zhen Miao; Ji-hua Wang; Su-Ping Qu; Qiang Yuan; Shen-chong Li (Horticulture, Environment, and Biotechnology, 2018)

Distribution, relationship, and risk assessment of toxic heavy metals in walnuts and growth soil - Yongxiang Han; Zhanglin Ni; Shiliang Li; Minghua Qu; Fubin Tang; Runhong Mo; Caifen Ye; Yihua Liu (Environmental Science and Pollution Research, 2018)

Study on the relationship between genetic variation of DNA methylation and heterosis in soybean leaves - Yuanqian Wang; Kaixin Zhang; Lifang Sun; Xiao Han; Sujie Fan; Xueying Li; Yiwei Qu; Dan Yao; Piwu Wang; Jun Zhang (Euphytica, 2018)

Iodine-Rich Herbs and Potassium Iodate Have Different Effects on the Oxidative Stress and Differentiation of TH17 Cells in Iodine-Deficient NOD.H-2h4 Mice - Cheng-han Gao; Jin-qiao Qu; Xi-yu Zhou; Tian-shu Gao (Biological Trace Element Research, 2018)

AMPK/NF-κB signaling pathway regulated by ghrelin participates in the regulation of HUVEC and THP1 Inflammation - Min Zhang; Shuping Wang; Zhicheng Pan; Tiantong Ou; Jianwei Ma; Hua Liu; Ruogu Li; Ping Yang; Wenzheng Han; Shaofeng Guan; Xumin Hou; Weiyi Fang; et al. (Molecular and Cellular Biochemistry, 2018)

Effect of corticosteroids on atrial fibrillation after catheter ablation: a meta-analysis - Sanjay Jaiswal; Xian-bao Liu; Qu-cheng Wei; Ying-hao Sun; Li-han Wang; Liu-guang Song; Dan-dan Yang; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Plipastatin and surfactin coproduction by Bacillus subtilis pB2-L and their effects on microorganisms - Ling Gao; Jinzhi Han; Hongxia Liu; Xiaoxu Qu; Zhaoxin Lu; Xiaomei Bie (Antonie van Leeuwenhoek, 2017)

Metagenomic analysis reveals the influences of milk containing antibiotics on the rumen microbes of calves - Wei Li; Yunsheng Han; Xue Yuan; Guan Wang; Zhibo Wang; Qiqi Pan; Yan Gao; Yongli Qu (Archives of Microbiology, 2017)

Temporal 18 O and deuterium variations in hydrologic components of a small watershed during a typhoon event - Simin Qu; Yifan Wang; Minmin Zhou; Han Liu; Peng Shi; Zhongbo Yu; Long Xiang (Isotopes in Environmental and Health Studies, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

The ecological adaptability of Phragmites australis to interactive effects of water level and salt stress in the Yellow River Delta - Bo Guan; Junbao Yu; Aixin Hou; Guangxuan Han; Guangmei Wang; Fanzhu Qu; Jiangbao Xia; Xuehong Wang (Aquatic Ecology, 2017)

Salidroside accelerates fracture healing through cell-autonomous and non-autonomous effects on osteoblasts - Xiao Qin Guo; Lin Qi; Jing Yang; Yue Wang; Chuan Wang; Zong Min Li; Ling Li; Ye Qu; Dan Wang; Ze Min Han (Cell and Tissue Research, 2017)

A strategy for introducing an endangered plant Mosla hangchowensis to urban area based on nitrogen preference - Mei-Ying Fan; Kai-Xuan Pan; Wen-Juan Han; Yi-Jun Lu; Qi Shen; Meng Wang; Yuan Ren; Ze-Long Qu; Jie Chang; Ying Ge (Acta Physiologiae Plantarum, 2016)

Chicken gga-miR-130a targets HOXA3 and MDFIC and inhibits Marek’s disease lymphoma cell proliferation and migration - Bo Han; Ling Lian; Xin Li; Chunfang Zhao; Lujiang Qu; Changjun Liu; Jiuzhou Song; Ning Yang (Molecular Biology Reports, 2016)

Targeting AMPK signalling pathway with natural medicines for atherosclerosis therapy: an integration of in silico screening and in vitro assay - Tiantong Ou; Xumin Hou; Shaofeng Guan; Jinjie Dai; Wenzheng Han; Ruogu Li; Wenxia Wang; Xinkai Qu; Min Zhang (Natural Product Research, 2016)

Manufacturer identification and storage time determination of “Dong’e Ejiao” using near infrared spectroscopy and chemometrics - Wen-long Li; Hai-fan Han; Lu Zhang; Yan Zhang; Hai-bin Qu (Journal of Zhejiang University-SCIENCE B, 2016)

Combination of PPT with LiCl Treatment Prevented Bilateral Ovariectomy-Induced Hippocampal-Dependent Cognition Deficit in Rats - Na Qu; Xiang-Yu Zhou; Li Han; Lei Wang; Jia-Xin Xu; Teng Zhang; Jiang Chu; Qiao Chen; Jian-Zhi Wang; Qi Zhang; Qing Tian (Molecular Neurobiology, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Evolutionary history of Apocheima cinerarius (Lepidoptera: Geometridae), a female flightless moth in northern China - Shuxian Liu; Nan Jiang; Dayong Xue; Rui Cheng; Yanhua Qu; Xinxin Li; Fumin Lei; Hongxiang Han (Zoologica Scripta, 2016)
The alterations in the phylogeographical structures of insects in response to the uplift of the Qinghai–Tibet Plateau and the Quaternary glaciations in eastern Asia, particularly in northern China, remain largely unknown. In this study, we selected Apocheima cinerarius , a moth with flightless females, using molecular data (complete mitochondrial genomes and nuclear data) and ecological niche modelling ( ENM ) to investigate the effects of paleoclimatic changes on the evolutionary history of insects in the area of northern China. The phylogenetic tree of complete mitochondrial genomes indicated that there were two lineages, the western and eastern lineages. The nuclear gene analyses also detected unique haplotypes in each lineage. Time of the most recent common ancestor ( TMRCA ) of the two lineages was approximately in Early–Middle Pleistocene. Bayesian skyline plots revealed that the western lineage underwent a population expansion event after the Last Glacial Maximum, whereas the eastern lineage underwent expansion between the Last Interglacial and the Last Glacial Maximum. Our results suggest that A. cinerarius expanded eastward from western sites until the moth was distributed across the entire region of northern China. Then, A . cinerarius underwent contraction into isolated glacial refugia followed by subsequent expansion driven by Pleistocene climate changes, which established a narrow sympatric area. Our results indicate that the Quaternary environmental fluctuations had profound influences on the diversification and demography of an insect in northern China, and the same species in north‐western China and north‐eastern China have different demographic histories.

Role of inflammation in the process of clinical Kashin-Beck disease: latest findings and interpretations - Jing Han; Weizhuo Wang; Chengjuan Qu; Ruiyu Liu; Wenrong Li; Zongqiang Gao; Xiong Guo (Inflammation Research, 2015)

The Domain II S4-S5 Linker in Nav1.9: A Missense Mutation Enhances Activation, Impairs Fast Inactivation, and Produces Human Painful Neuropathy - Chongyang Han; Yang Yang; Bianca T. A. de Greef; Janneke G. J. Hoeijmakers; Monique M. Gerrits; Camiel Verhamme; Jian Qu; Giuseppe Lauria; Ingemar S. J. Merkies; Catharina G. Faber; Sulayman D. Dib-Hajj; Stephen G. Waxman (NeuroMolecular Medicine, 2015)

Potent CDC25B and PTP1B phosphatase inhibitors: 2′,4′,6′-trihydroxylchalcone derivatives - Shui-Lian Zhao; Zhou Peng; Xing-Hua Zhen; Hong-Guo Jin; Yan Han; You-Le Qu; Li-Ping Guan (Medicinal Chemistry Research, 2015)

New maltol glycosides from Flos Sophorae - Yi Zhang; Lu Qu; Lili Liu; Xiaoxia Li; Erwei Liu; Lifeng Han; Shiming Fang; Xiumei Gao; Tao Wang (Journal of Natural Medicines, 2015)

Blockade of the Activation of T Cells Around β-Cell by the Targeted CTLA-4 Ig at the Surface of β-Cell - Wei Qu; Lin Li; Chendong Han; Meihua Li; Jing Wang; Chaohui Yin; Jing Zhang; Zhaoshun Jiang (Cell Biochemistry and Biophysics, 2015)

Identification of QTLs associated with salt or alkaline tolerance at the seedling stage in rice under salt or alkaline stress - Jing-long Liang; Ying-ping Qu; Chun-gang Yang; Xiao-ding Ma; Gui-lan Cao; Zheng-wu Zhao; San-yuan Zhang; Tao Zhang; Long-zhi Han (Euphytica, 2015)

Effects of Olanzapine–Fluoxetine Combination Treatment of Major Depressive Disorders on the Quality of Life During Acute Treatment Period - Wei Qu; Shanshan Gu; Han Luo; Qianying Tang; Junwei Guo (Cell Biochemistry and Biophysics, 2014)

Understanding historical and current patterns of species richness of babblers along a 5000‐m subtropical elevational gradient - Yongjie Wu; Robert K. Colwell; Naijian Han; Ruiying Zhang; Wenjuan Wang; Qing Quan; Chunlan Zhang; Gang Song; Yanhua Qu; Fumin Lei (Global Ecology and Biogeography, 2014)
Aim To understand the causes of historical and current elevational richness patterns of L eiothrichinae babblers, a diverse and mostly endemic group of birds. Location A 5000‐m elevational gradient in the H engduan M ountains, C hina. Methods By means of a dated phylogenetic tree and reconstructed ancestral states, we estimated elevation‐specific diversification rate, applied a new method to estimate colonization frequency and age and, for the first time, modelled historical species richness patterns that take account of temporal patterns of palaeotemperature. As explanations for current richness patterns, we assessed area, geometric constraints, temperature, precipitation, seasonality and productivity. Results The current elevational pattern of species richness is a hump‐shaped curve with a peak at about 1000–2500 m. The reconstructed palaeopatterns of species richness suggest that babblers, as a clade, first occupied the H engduan M ountains at low to mid‐elevations, although the method of ancestral state reconstruction cannot conclusively reject origins outside the current elevational distribution of the group. Diversification rates varied little along the elevational gradient, and thus cannot explain the richness pattern, but historical colonization frequency and colonization age were highly correlated with present‐day species richness. Seasonality and productivity had greater power than area and geometric constraints in explaining the present‐day richness pattern of babblers along the elevational gradient. Conclusions Historical and modern factors have both played important roles in shaping species richness patterns. Reconstructed historical richness patterns suggest that babblers first diversified in the H engduan M ountains at low to mid elevations, but richness patterns almost certainly shifted substantially under changing climates of the past 10 M yr. The current richness patterns of babblers are associated with seasonality and productivity, but they are also a product of historical evolutionary and ecological dynamics. The methods we introduce for assessing historical colonization rates and past patterns of richness offer promise for understanding other elevational richness gradients.

Analysis of the microclimate and CO2 flux characteristics in arid desert wetland ecosystem in summer: A case study in Xihu desert wetland, Dunhuang, China - Qian-Qian Gou; Jian-Jun Qu; Zhi-Wen Han (Journal of Earth System Science, 2014)

Isolation and characterization of fucoidans from five brown algae and evaluation of their antioxidant activity - Guiyan Qu; Xu Liu; Dongfeng Wang; Yi Yuan; Lijun Han (Journal of Ocean University of China, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

The Effect of Air Density on Sand Transport Structures and the Adobe Abrasion Profile: A Field Wind-Tunnel Experiment Over a Wide Range of Altitude - Qingjie Han; Jianjun Qu; Zhibao Dong; Ruiping Zu; Kecun Zhang; Hongtao Wang; Shengbo Xie (Boundary-Layer Meteorology, 2014)

Differences in oxygen-18 and deuterium content of throughfall and rainfall during different flood events in a small headwater watershed - Simin Qu; Minmin Zhou; Peng Shi; Han Liu; Weimin Bao; Xi Chen (Isotopes in Environmental and Health Studies, 2014)

Molecular cloning, expression, purification and characterization of thioredoxin from Antarctic sea-ice bacteria Pseudoalteromonas sp. AN178 - Quanfu Wang; Yanhua Hou; Junjie Qu; Yanyan Hong; Yifei Lin; Xiao Han (Molecular Biology Reports, 2013)

Vulnerability of population and transportation infrastructure at the east bank of Delaware Bay due to coastal flooding in sea-level rise conditions - Han Song Tang; Steven I-Jy Chien; Marouane Temimi; Cheryl Ann Blain; Qu Ke; Liuhui Zhao; Simon Kraatz (Natural Hazards, 2013)

Two endosymbiotic bacteria, Wolbachia and Arsenophonus, in the brown planthopper Nilaparvata lugens - Lv-Yu Qu; Yi-Han Lou; Hai-Wei Fan; Yu-Xuan Ye; Hai-Jian Huang; Meng-Qi Hu; Ya-Ni Zhu; Chuan-Xi Zhang (Symbiosis, 2013)

Synthesis of novel 4-thiazolidione derivatives as antibacterial agents against drug-resistant Staphylococcus epidermidis - Dan Zhao; Huayong Liu; Likang Zheng; Guozhen He; Di Qu; Shiqing Han (Medicinal Chemistry Research, 2013)

Iodine Excess Induces Hepatic Steatosis Through Disturbance of Thyroid Hormone Metabolism Involving Oxidative Stress in BaLB/c Mice - Yun Xia; Wei Qu; Li-Na Zhao; Hao Han; Xue-Feng Yang; Xiu-Fa Sun; Li-Ping Hao; Jian Xu (Biological Trace Element Research, 2013)

Occurrence of several main antibiotic residues in raw milk in 10 provinces of China - Nan Zheng; Jiaqi Wang; Rongwei Han; Xiaomin Xu; Yunpeng Zhen; Xueyin Qu; Peng Sun; Songli Li; Zhongnuo Yu (Food Additives & Contaminants Part B-Surveillance, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

SENP2 regulates MEF2A de-SUMOylation in an activity dependent manner - Han Lu; Bin Liu; Shengwu You; Lei Chen; Qu Dongmei; Minjie Gu; Yan Lu; Yingyi Chen; Fujun Zhang; Buwei Yu (Molecular Biology Reports, 2013)

C-Terminal Membrane Association of Bestrophin 3 and Its Activation as a Chloride Channel - Xiaohua Han; Zhiqiang Qu; Junxia Xie; Hong Jiang (The Journal of Membrane Biology, 2013)

Deletion of RBP-J in dendritic cells compromises TLR-mediated DC activation accompanied by abnormal cytoskeleton reorganization - Yun-Ru Chen; Fan Feng; Li Wang; Shuo-Yao Qu; Zhen-Qiang Zhang; Li Liu; Hong-Yan Qin; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2013)

Analysis of Aztreonam-Inducing Proteome Changes in Nondividing Filamentous Helicobacter pylori - Chunhong Shao; Yabin Zhou; Yundong Sun; Hongyan Wang; Wei Qu; Han Yu; Chunyan Chen; Jihui Jia (Current Microbiology, 2012)

Firing pattern and synchronization property analysis in a network model of the olfactory bulb - Ying Du; Rubin Wang; Fang Han; Qishao Lu; Jingyi Qu (Cognitive Neurodynamics, 2012)

Feathered sand ridges in the Kumtagh Desert and their position in the classification system - JianJun Qu; KongTai Liao; GuangRong Dong; QingHe Niu; ZheFan Jing; QinJie Han (Science China Earth Sciences, 2011)

Cloning and characterization of a wheat neutral ceramidase gene Ta-CDase - Xiumei Yu; Xiaojie Wang; Xueling Huang; Heinrich Buchenauer; Qingmei Han; Jun Guo; Jie Zhao; Zhipeng Qu; Lili Huang; Zhensheng Kang (Molecular Biology Reports, 2011)

Variation in the PTEN-induced putative kinase 1 gene associated with the increase risk of type 2 diabetes in northern Chinese - YANCHUN QU; LIANG SUN; ZE YANG; RUIFA HAN (Journal of Genetics, 2011)

Wheat defense genes in fungal (Puccinia striiformis) infection - Xiumei Yu; Xiaojie Wang; Chenfang Wang; Xianming Chen; Zhipeng Qu; Xiudao Yu; Qingmei Han; Jie Zhao; Jun Guo; Lili Huang; Zhensheng Kang (Functional & Integrative Genomics, 2010)

Hypoglycemic Activity of Grifola frondosa Rich in Vanadium - Bo Cui; Linna Han; Jingran Qu; Yingtao Lv (Biological Trace Element Research, 2009)

Comparison of Vanadium-Rich Activity of Three Species Fungi of Basidiomycetes - Chunchao Han; Bo Cui; Jingran Qu (Biological Trace Element Research, 2009)

A phylogenetic analysis of laughingthrushes (Timaliidae: Garrulax ) and allies based on mitochondrial and nuclear DNA sequences - Xu Luo; Yan Hua Qu; Lian Xian Han; Shou Hsien Li; Fu Min Lei (Zoologica Scripta, 2009)
The interspecific relationships among extant laughingthrushes have been unclear for a long time and this has resulted in a confusing taxonomic history. Recent advances in molecular methods have greatly improved the resolution of the phylogeny of birds; however, little works has been done on this specific group because of the inaccessibility to many species. This diverse group includes 50 species mostly distributed in South China and South‐east Asia, and were traditionally arranged into the genus Garrulax , for which the non monophyly had been questioned by previous molecular studies. In this study, we infer a phylogeny for 23 Garrulax species and 20 species from close related genera. Mitochondrial data or combined with nuclear sequences both indicate paraphyly of Garrulax , dividing Garrulax species into two groups. Based on these results, we suggest resurrecting the genus name Trochalopteron Blyth, 1843 for one group and retaining Garrulax for the other pending further study. Using dating methods with a secondary calibration point, we develop a profile of the speciation history of laughingthrushes, which suggests that the Hengduan Mountains might not be the centre of origin for these birds as previously suggested.

The Influence of Surface Trapping and Dark States on the Fluorescence Emission Efficiency and Lifetime of CdSe and CdSe/ZnS Quantum Dots - Hong-Mei Gong; Zhang-Kai Zhou; Hao Song; Zhong-Hua Hao; Jun-Bo Han; Yue-Ying Zhai; Si Xiao; Qu-Quan Wang (Journal of Fluorescence, 2007)

The hepatitis B virus protein MHBs(t) sensitizes hepatoma cells to TRAIL-induced apoptosis through ERK2 - Xiaohong Liang; Juan Du; Yugang Liu; Min Cui; Chunhong Ma; Lihui Han; Zhonghua Qu; Zhiyong Zhang; Zhaohui Sun; Lining Zhang; Youhai H. Chen; Wensheng Sun (Apoptosis, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

N2O Emissions under Different Moisture and Temperature Regimes - Han Jian-gang; Zhu Yong-li; Bai Hong-ying; Qu Dong; Chu Jin-yu; Wu Chun-du (Bulletin of Environmental Contamination and Toxicology, 2007)